Battery Flash Recycling

JP2024506619A5Active Publication Date: 2025-02-07WILLIAM MARCH RICE UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023547834
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-03
Filing Date
2022-02-08
Publication Date
2025-02-07
Estimated Expiration
2042-02-08

AI Technical Summary

Technical Problem

Current recycling methods for lithium-ion batteries require high-temperature furnaces or harsh wet extraction processes, which destroy the cathode's three-dimensional morphology, leading to low metal recovery rates and environmental impact, while the increasing demand for batteries depletes metal reserves.

Method used

A solvent-free and water-free flash Joule heating process combined with magnetic separation to recover metals from cathodes, preserving the 3D layered structure and forming a conductive carbon coating for improved electrochemical stability.

Benefits of technology

Achieves high metal recovery rates of up to 98% with preserved cathode structure, reducing energy and greenhouse gas emissions, and enabling efficient reconstitution into new cathodes with enhanced performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

A method and system for flash recycling of batteries, such as lithium ion batteries, other metal (sodium, potassium, zinc, magnesium, and aluminum) ion batteries, metal batteries, batteries with all metal oxide cathodes, and batteries with anodes containing graphite. The method and system includes a solvent-free and water-free flash joule heating (FJH) method performed on a mixture containing materials from the battery, which is performed in milliseconds to recycle the materials. In some embodiments, the FJH method can be combined with magnetic separation to recover lithium, cobalt, nickel, and manganese in yields as high as 98%. In some embodiments, the FJH method is followed by a rinse with a dilute acid, such as 0.01M HCl. In other embodiments, the FJH method is utilized to purify graphite in batteries, for example, for use in battery anodes.
Need to check novelty before this filing date? Find Prior Art

Description

Related Applications

[0001] CROSS REFERENCE TO RELATED PATENT APPLICATIONS

[0001] This application claims priority to (a) U.S. Patent Application No. 63 / 147,069, entitled "Recycling Of Spent Batteries By Flash Joule Heating," filed February 8, 2021, to James M. Tour et al., and (b) U.S. Patent Application No. 63 / 285,952, entitled "Flash Recycling Of Batteries," filed December 3, 2021, to James M. Tour et al., each of which is commonly owned by the present invention owner. These patent applications are incorporated herein in their entirety. [Technical field]

[0002] STATEMENT REGARDING FEDERALLY FUNDED RESEARCH This invention was made with government support under Grant No. FA9550-19-1-0296 awarded by the United States Air Force Office of Scientific Research and Grant No. DE-FE0031794 awarded by the United States Department of Energy, National Energy Technology Laboratory. The Government has certain rights in this invention.

[0003]

[0003] The present invention relates to flash recycling of batteries, such as lithium-ion batteries, other metal (sodium, potassium, zinc, magnesium, and aluminum)-ion batteries, metal batteries (e.g., solid-state lithium batteries), batteries with all-metal oxide cathodes, and batteries with all-graphite-containing anodes. Flash recycling is characterized by a solvent-free and water-free flash joule heating (FJH) process, sometimes performed in combination with magnetic separation to recover, for example, lithium, cobalt, nickel, manganese, etc., at the cathode, and further characterized by the FJH process to purify graphite in the battery, for example, graphite in the anode. [Background technology]

[0004] background

[0004] Due to the continuous accumulation of spent Li-ion batteries (LIBs) and the increasing scarcity of their useful metal sources, effective recycling strategies have been urgently sought. [Tran 2019; Lv 2018; Xu 2020]. Current recycling methods can achieve high recovery rates of useful metals, but they require high-temperature furnaces or harsh wet extraction methods, destroying the entire three-dimensional (3D) morphology of the cathode, making these methods economically and environmentally unattractive. [Lv 2018; Natarajan 2018]. Therefore, with less than 5% of LIBs being recycled, there will always be a need to mine metals from their ores. [Recycle 2019; Velazquez 2019; Li 2017].

[0005]

[0005] The ever-increasing demand for portable electronic devices and electric vehicles is accelerating the commercial production of secondary batteries, especially LIBs. [Recycle 2019;Andre 2015]. The market for rechargeable LIBs is expected to reach approximately $50 billion in 2020 and $70 billion in 2022. [Zou 2013]. The foreseeable staggering accumulation of used LIBs is disconcerting, as most LIBs have an expected lifespan of less than 10 years, often only 2 years. [Salvatierra 2021;Chen 2020]. [Recycle 2019;Velazquez 2019;Li 2017]. Moreover, at the projected pace of Li and Co mining, global reserves of these elements are projected to be depleted by 2050 and 2030, respectively. [Natarajan 2018;Jacoby 2020]. Spent cathodes consist of Li and transition metals, which account for about 35% of the total weight and 45% of the cost of LIBs. Effective recycling of spent cathodes would reduce the need for remote mining of these metals, reduce the environmental impact of LIB disposal, and provide an economic incentive for recycling. [He 2016]. The anode is graphite, which is cheaper than the cathode, but using a form of battery-grade graphite, natural sources of battery-grade graphite cost $10,000 per ton, and the preferred synthetic battery-grade graphite can cost as much as $20,000 per ton. In addition, spent anodes have several weight percent lithium and residual leached cathode metals in them, which have a higher metal content than mined ores. Therefore, from an environmental perspective, it cannot simply be landfilled, and from an economic perspective, it is attractive to recycle the components as well. Summary of the Invention

[0006]

[0006] The present invention relates to a method and system for a solvent-free and water-free flash joule heating (FJH) process performed on a mixture containing materials from lithium-ion batteries, other metal-ion batteries, metal batteries, batteries with all-metal oxide cathodes, and batteries with all-graphite-containing anodes, performed in milliseconds. In some embodiments, the FJH process is combined with magnetic separation to recover lithium, cobalt, nickel, manganese, etc., with yields as high as 98%. This process is called "flash recycling". Spent LIBs with different chemistries, namely lithium cobalt oxide (LCO), lithium nickel-manganese-cobalt oxide (NMC), and both LCO and NMC mixed together, can be effectively flash recycled. Characterization of the flash recycling products reveals intact 3D layered core structures with hierarchical structures, thus greatly simplifying the reconstitution into new cathodes. The flash process has further been shown to produce a lithium-ion permeable conductive carbon coating on the flash cathode material, thereby imparting improved electrochemical stability to the flash cathode material. A life cycle analysis for current recycling processes highlights that flash recycling can be made an economically advantageous process while significantly reducing total energy and greenhouse gas (GHG) emissions.

[0007] In another embodiment, the FJH method is used to purify graphite in metal ion batteries, such as in anodes.

[0008] In general, in one embodiment, the invention features a method of recovering metals. The method includes forming a mixture including a cathode material. The cathode material is prepared from one or more batteries. The method further includes applying a voltage across the mixture to obtain the metal and cathode waste from the cathode material. The voltage is applied in one or more voltage pulses. The duration of each of the one or more voltage pulses is for a period of predetermined duration. The method further includes magnetically separating the metal and the cathode waste.

[0008]

[0009] Implementations of the invention may include one or more of the following features.

[0010] The metal may include a cathode metal selected from the group consisting of lithium, cobalt, nickel, manganese, iron, and combinations thereof.

[0009]

[0011] The metal comprises a cathodic metal selected from the group consisting of metal oxides, metal salts, metal carbonates, metal phosphates, and combinations thereof.

[0012] The cathode metal may include a metal oxide.

[0010]

[0013] The metal oxide may include cobalt oxide.

[0014] The cathode metal may include a metal carbonate.

[0015] The metal carbonate may include lithium carbonate.

[0011]

[0016] The cathode metal may include a metal phosphate.

[0017] The metal phosphate may include iron phosphate.

[0018] The one or more batteries can include a battery selected from the group consisting of a lithium ion battery, a sodium ion battery, a potassium ion battery, a zinc ion battery, a magnesium ion battery, an aluminum ion battery, a metal ion battery, a metal battery, an anodeless battery, a metal oxygen battery, a metal air battery, and combinations thereof.

[0012]

[0019] The one or more batteries may include one or more lithium ion batteries.

[0020] The one or more lithium ion batteries may each include a lithium ion battery having a lithium cobalt oxide (LCO) cathode or a lithium nickel manganese cobalt oxide (NMC) cathode.

[0013]

[0021] Each of the one or more lithium ion cells may include a respective LCO cathode.

[0022] Each of the one or more lithium ion batteries may include a respective NMC cathode.

[0014]

[0023] The metal obtained by applying the voltage may include a cathodic metal, including a metal phosphate.

[0024] The metal phosphate may include iron phosphate.

[0015]

[0025] Each of the portions of the one or more lithium ion batteries may include an LCO cathode, and each of the portions of the one or more lithium ion batteries may include an NMC cathode.

[0016]

[0026] The one or more lithium ion batteries may include a lithium ion battery having a cathode comprising a mixture of lithium cobalt oxide (LCO) and lithium nickel manganese cobalt oxide (NMC).

[0017]

[0027] The mixture may further include a conductive additive.

[0028] The conductive additive may be a carbon source.

[0029] The conductive additive may be selected from the group consisting of graphite, anode graphite, battery grade graphite, elemental carbon, carbon black, graphene, flash graphene, turbostratic graphene, coal, anthracite, coke, metallurgical coke, calcined coke, activated carbon, -biochar, carbon from natural gas with hydrogen atoms removed, activated carbon, shungite, plastic waste, carbon char from plastic waste, food waste, carbon char from food waste, biomass, biomass-derived carbon char, carbon char from hydrocarbon gases, and mixtures thereof.

[0018]

[0030] The conductive additive may be carbon black.

[0031] The conductive additive may be primarily elemental carbon.

[0032] The conductive additive may be selected from the group consisting of metals, metal salts, metal oxides, metalloids, metal complexes, conductive phosphorus, and non-metallic conductive materials.

[0019]

[0033] The conductive additive may be selected from the group consisting of metals, metal salts, metal oxides, metalloids, and metal complexes.

[0034] The conductive additive may be a metalloid.

[0020]

[0035] The metalloid may be selected from the group consisting of B, Si, As, Te, and At.

[0036] The conductive additive may be prepared from one or more of the battery's anode materials.

[0021]

[0037] The conductive additive may be prepared from one or more batteries.

[0038] The cathode material and the conductive additive may be mixed in a weight ratio ranging from 1:2 to 25:1.

[0022]

[0039] The applied voltage may be in the range of 15V to 300V.

[0040] The mass of the mixture to which the voltage is applied may be greater than 1 kg. The applied voltage may be between 100V and 100,000V.

[0023]

[0041] The mass of the mixture to which the voltage is applied may be greater than 100 kg.

[0042] The mass of the mixture to which the voltage is applied may be greater than 1 kg. The current applied may be between 1,000 amp and 30,000 amp.

[0024]

[0043] The mass of the mixture to which the voltage is applied may be greater than 100 kg.

[0044] The mixture may have a resistance in the range of 0.1 ohms to 25 ohms when a voltage is applied.

[0025]

[0045] The period of time for each duration of the one or more voltage pulses may be between 1 microsecond and 25 seconds.

[0046] The period of time for each duration of the one or more voltage pulses may be between 1 microsecond and 10 seconds.

[0026]

[0047] The period of time for each duration of the one or more voltage pulses may be between 1 microsecond and 1 second.

[0048] The duration of each of the one or more voltage pulses may be between 100 microseconds and 500 microseconds.

[0027]

[0049] The one or more voltage pulses may be between 2 voltage pulses and 100 voltage pulses.

[0050] The voltage pulse can be implemented using direct current (DC).

[0028]

[0051] The method may be carried out using a pulsed direct current (PDC) Joule heating process.

[0052] The voltage pulses can be implemented using alternating current (AC).

[0029]

[0053] The voltage pulses can be implemented using both direct current (DC) and alternating current.

[0054] The method can alternate between using direct current (DC) and alternating current (AC).

[0030]

[0055] The method can use direct current (DC) and alternating current (AC) simultaneously.

[0056] One or more voltage pulses can increase the temperature of the mixture to at least 3000K.

[0031]

[0057] The metal obtained by applying a voltage across the mixture may include metal particles having a carbon coating.

[0058] The carbon coating may be electrically conductive.

[0032]

[0059] The carbon coating may be ion-permeable.

[0060] The carbon coating may be electrically conductive and may be ion-permeable.

[0061] The carbon coating may be ion-permeable for metal ions.

[0033]

[0062] The metal ions may be selected from the group consisting of lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, and aluminum ions.

[0034]

[0063] The carbon coating may be amorphous.

[0064] The carbon coating may include graphene.

[0065] The method can preserve the 3D layer structure of the cathode in the cathode material.

[0035]

[0066] The method can preserve the 3D morphology of the cathode in the cathode material.

[0067] The method can destroy the 3D morphology of the cathode in the cathode material.

[0068] The method may further include a cooling step, which may cool the metal and cathode waste prior to the step of magnetically separating the metal and cathode waste.

[0036]

[0069] The metal and cathode waste may be in a weight ratio of 20:1 to 5:1.

[0070] The metal and cathode waste may be in a weight ratio of 10:1 to 8:1.

[0071] The method may further include applying a second voltage across the cathodic waste after the mechanically separating step. The second voltage may be applied in one or more second voltage pulses. The duration of each of the one or more second voltage pulses may be for a period of the second duration.

[0037]

[0072] The second voltage may be the same as the voltage applied across the cathodic material. The period of the second duration may be the same as the period of the duration of the voltage applied across the cathodic material.

[0038]

[0073] Applying a second voltage across the cathode waste can capture additional metal and the reduced portion of the cathode waste. The method may further include magnetically separating the additional metal and the reduced portion of the cathode waste.

[0039]

[0074] The further metal and the reduced portion of the cathode waste may be in a weight ratio of at least 1:1.

[0075] The further metal and the reduced portion of the cathode waste may be in a weight ratio of at least 1.5:1.

[0040]

[0076] The method may further comprise recovering the metals by separating them from the cathode waste and then collecting them.

[0077] The cathode material may include a first mass of a cathode metal selected from the group consisting of lithium, cobalt, nickel, magnesium, and combinations thereof. The collected metal may comprise at least 70 wt% of the first mass of the cathode metal.

[0041]

[0078] The collected metal may comprise at least 70 wt% of the lithium in the first mass of cathode metal.

[0079] The collected metal may comprise at least 70 wt% of the cobalt in the first mass of cathode metal.

[0042]

[0080] The collected metal may comprise at least 70 wt% of the nickel in the first mass of cathode metal.

[0081] The collected metal may comprise at least 70 wt% of the magnesium in the first mass of cathode metal.

[0043]

[0082] The collected metals may include at least 70 wt% of each of the lithium, cobalt, nickel, and magnesium in the first mass of cathode metal.

[0083] The collected metal may comprise at least 90 wt% of the lithium in the first mass of cathode metal.

[0044]

[0084] The collected metal may comprise at least 90 wt% of the cobalt in the first mass of cathode metal.

[0085] The collected metal may comprise at least 90 wt% of the nickel in the first mass of cathode metal.

[0045]

[0086] The collected metal may comprise at least 90 wt% of the magnesium in the first mass of cathode metal.

[0087] The collected metals may include at least 90 wt% of each of the lithium, cobalt, nickel, and magnesium in the first mass of cathode metal.

[0046]

[0088] The method can be carried out in a continuous or automated process.

[0089] The metals may be recycled into new metal-ion or metal batteries.

[0090] The metal may be recycled as a cathode material in new metal-ion or metal batteries.

[0047]

[0091] In general, in another embodiment, the invention features a method of recovering metals. The method includes forming a mixture including a cathode material. The cathode material is prepared from one or more batteries. The method further includes applying a voltage across the mixture to obtain the metal and cathode waste from the cathode material. The voltage is applied in one or more voltage pulses. The duration of each of the one or more voltage pulses is for a period of predetermined duration. The method further includes magnetically separating the metal and the cathode waste.

[0048]

[0092] Implementations of the invention may include one or more of the following features.

[0093] The one or more batteries may be one or more non-lithium metal ion batteries.

[0049]

[0094] The one or more batteries may include one or more batteries selected from the group consisting of lithium ion batteries, sodium ion batteries, potassium ion batteries, zinc ion batteries, magnesium ion batteries, aluminum ion batteries, metal ion batteries, metal batteries, anodeless batteries, metal oxygen batteries, metal air batteries, and combinations thereof.

[0050]

[0095] In general, in another embodiment, the invention features a system for carrying out a method of recovering metals utilizing at least one of the methods described above for recovering metals. The system includes a source of a mixture including a cathode material. The system further includes a cell operably connected to the source, such that the mixture flows through the cell and is held under compression. The system further includes an electrode operably connected to the cell. The system further includes a flash power supply for applying a voltage across the mixture to obtain metals and cathode waste from the cathode material. The system further includes a magnet in operable contact with the metals and cathode waste. The magnet is operable in response to magnetically separating the metals and cathode waste.

[0051]

[0096] Implementations of the invention may include one or more of the following features.

[0097] In general, in another embodiment, the invention features a method for producing a method of treating a cancer.

[0098] Implementations of the invention may include one or more of the following features.

[0052]

[0099] The mixture may further include a conductive additive.

[0100] The system may be operable to carry out a continuous or automated process.

[0053]

[0101] In general, in another embodiment, the invention features a method of recovering metals. The method includes forming a mixture including battery material. The battery material is prepared from one or more batteries. The method further includes applying a voltage across the mixture to obtain the metals and battery waste from the battery material. The voltage is applied in one or more voltage pulses. The duration of each of the one or more voltage pulses is for a period of predetermined duration. The method further includes magnetically separating the metals and battery waste.

[0054]

[0102] Implementations of the invention may include one or more of the following features.

[0103] The one or more batteries may include one or more lithium ion batteries.

[0055]

[0104] The one or more batteries may include one or more non-lithium metal ion batteries selected from the group consisting of lithium ion batteries, sodium ion batteries, potassium ion batteries, zinc ion batteries, magnesium ion batteries, aluminum ion batteries, metal ion batteries, metal batteries, batteries without an anode, metal oxygen batteries, metal air batteries, and combinations thereof.

[0056]

[0105] The mixture may further include a conductive additive.

[0106] In general, in another embodiment, the invention features a system for carrying out a method of recovering metals utilizing the methods described above for recovering metals. The system includes a source of a mixture including battery material. The system further includes a cell operably connected to the source such that the mixture flows through the cell and is held under compression. The system further includes an electrode operably connected to the cell. The system further includes a flash power source for applying a voltage across the mixture to obtain the metals and battery waste from the battery material. The system further includes a magnet in operable contact with the metals and battery waste. The magnet is operable in response to magnetically separating the metals and battery waste.

[0057]

[0107] Implementations of the invention may include one or more of the following features.

[0108] The battery materials may include lithium ion battery materials.

[0109] The battery material may be a non-lithium metal ion battery material selected from the group consisting of sodium ion battery materials, potassium ion battery materials, zinc ion battery materials, magnesium ion battery materials, aluminum ion battery materials, and combinations thereof.

[0058]

[0110] The mixture may further include a conductive additive.

[0111] The system may be operable to carry out a continuous or automated process.

[0059]

[0112] In general, in another embodiment, the invention features a method of recovering metals. The method includes forming a mixture including a cathode material. The cathode material is prepared from one or more batteries including a cathode. The method further includes applying a voltage across the mixture to obtain metals and cathode waste from the cathode material. The voltage is applied in one or more voltage pulses. The duration of each of the one or more voltage pulses is for a period of predetermined duration. The method destroys the 3D morphology of the cathode in the cathode material. The method further includes extracting metals from the cathode waste using an aqueous solution.

[0060]

[0113] Implementations of the invention may include one or more of the following features.

[0114] The metal may be selected from the group consisting of lithium, cobalt, nickel, manganese, copper, and iron.

[0061]

[0115] The metal may be in the form of one or more metal salts.

[0116] The one or more metal salts may be in the form of one or more oxides.

[0062]

[0117] The aqueous solution may contain an acid.

[0118] The acid may be HCl in the range of 0.01M to 12M.

[0119] The acid may be HCl in the range of 0.01M to 0.1M.

[0063]

[0120] The acid may range from 0.01M to 15M.

[0121] The acid may be in the range of 0.01M to 0.1M.

[0122] The voltage can be applied in the range of 1 voltage pulse to 100 voltage pulses.

[0064]

[0123] The one or more cells including a cathode may include a cathode selected from the group consisting of an LCO cathode and an NMC cathode.

[0124] In general, in another embodiment, the invention features a system for carrying out a method of recovering metals utilizing at least one of the methods described above. The system includes a source of a mixture including a cathode material. The system further includes a cell operably connected to the source, such that the mixture flows through the cell and is held under compression. The system further includes an electrode operably connected to the cell. The system further includes a flash power supply for applying a voltage across the mixture to obtain metals and cathode waste from the cathode material. The system further includes a source of an aqueous solution. The aqueous solution is operative in response to extracting metals from the cathode waste.

[0065]

[0125] Implementations of the invention may include one or more of the following features.

[0126] The mixture may further include a conductive additive.

[0127] The system may be operable to carry out a continuous or automated process.

[0066]

[0128] In general, in another embodiment, the invention features a method of recycling anode material. The method includes obtaining a mixture including anode material from one or more batteries. The anode material includes graphite. The method further includes applying a voltage across the mixture to refine the graphite in the mixture. The voltage is applied in one or more voltage pulses. The duration of each of the one or more voltage pulses is for a period of predetermined duration. The method further includes utilizing the refined graphite by applying the voltage in one or more new batteries.

[0067]

[0129] Implementations of the invention may include one or more of the following features.

[0130] The one or more batteries may include one or more lithium ion batteries.

[0068]

[0131] The one or more batteries may include one or more batteries selected from the group consisting of lithium ion batteries, sodium ion batteries, potassium ion batteries, zinc ion batteries, magnesium ion batteries, aluminum ion batteries, metal ion batteries, and combinations thereof.

[0069]

[0132] The one or more new batteries may include one or more new lithium ion batteries.

[0133] The one or more new batteries may include one or more new lithium ion batteries.

[0070]

[0134] The one or more batteries may include one or more batteries selected from the group consisting of lithium ion batteries, sodium ion batteries, potassium ion batteries, zinc ion batteries, magnesium ion batteries, aluminum ion batteries, metal ion batteries, metal batteries, anodeless batteries, metal oxygen batteries, metal air batteries, and combinations thereof.

[0071]

[0135] The mixture may consist of an anode material.

[0136] The mixture may further include cathode materials from one or more of the batteries.

[0072]

[0137] The mixture may include an anode material mixed with a conductive additive that is not an anode material.

[0138] The conductive additive may be a carbon source.

[0073]

[0139] The conductive additive may be selected from the group consisting of graphite, anode graphite, battery grade graphite, elemental carbon, carbon black, graphene, flash graphene, turbostratic graphene, coal, anthracite, coke, metallurgical coke, calcined coke, activated carbon, biochar, carbon from natural gas with hydrogen atoms removed, activated carbon, shungite, plastic waste, carbon char from plastic waste, food waste, carbon char from food waste, biomass, carbon char from biomass, carbon from hydrocarbon gases, and mixtures thereof.

[0074]

[0140] The conductive additive may be carbon black.

[0141] The conductive additive may be primarily elemental carbon.

[0142] In general, in another embodiment, the invention features a system for carrying out a method of recycling anode material utilizing at least one of the methods of recycling anode material described above. The system includes a source of a mixture including anode material including graphite. The system further includes a cell operably connected to the source such that the mixture flows through the cell and is held under compression. The system further includes an electrode operably connected to the cell. The system further includes a flash power supply for applying a voltage across the mixture to refine the graphite in the anode material.

[0075]

[0143] Implementations of the invention may include one or more of the following features.

[0144] The anode material may include a lithium ion battery anode material.

[0145] The anode material may comprise a non-lithium metal ion battery anode material selected from the group consisting of a lithium ion battery anode material, a sodium ion battery anode material, a potassium ion battery anode material, a zinc ion battery anode material, a magnesium ion battery anode material, an aluminum ion battery anode material, and combinations thereof.

[0076]

[0146] The mixture may include an anode material mixed with a conductive additive that is not an anode material.

[0147] The system may be operable to carry out a continuous or automated process.

[0077]

[0148] In general, in another embodiment, the invention features a method that includes selecting a graphite anode material from a battery. The method further includes applying flash joule heating to the graphite anode material to form a flashed graphite anode material. The application of flash joule heating refines the graphite anode material.

[0078]

[0149] Implementations of the invention may include one or more of the following features.

[0150] The battery may be a lithium ion battery.

[0151] The battery may be a battery selected from the group consisting of a lithium ion battery, a sodium ion battery, a potassium ion battery, a zinc ion battery, a magnesium ion battery, an aluminum ion battery, and combinations thereof.

[0079]

[0152] The flash joule heating may include applying a voltage across the graphite anode material. The voltage may be applied in one or more voltage pulses. The duration of each of the one or more voltage pulses may be for a period of predetermined duration.

[0080]

[0153] The method may further include using the flashed graphite anode material in the second battery.

[0154] The second battery may be a second lithium ion battery.

[0081]

[0155] The battery may be a lithium ion battery.

[0156] The second battery may be a second non-lithium metal ion battery selected from the group consisting of a sodium ion battery, a potassium ion battery, a zinc ion battery, a magnesium ion battery, an aluminum ion battery, and combinations thereof.

[0082]

[0157] The battery may be a non-lithium metal ion battery selected from the group consisting of a sodium ion battery, a potassium ion battery, a zinc ion battery, a magnesium ion battery, an aluminum ion battery, and combinations thereof.

[0083]

[0158] The method may further include washing the flashed graphite anode material to separate inorganic metals and salts in the flashed graphite anode material from the graphite.

[0084]

[0159] The method may further include using the flushed graphite anode material in a second cell after cleaning.

[0160] The second battery may be a second lithium ion battery.

[0085]

[0161] The battery may be a lithium ion battery.

[0162] The second battery may be a battery selected from the group consisting of a lithium ion battery, a sodium ion battery, a potassium ion battery, a zinc ion battery, a magnesium ion battery, an aluminum ion battery, and combinations thereof.

[0086]

[0163] The battery may be a battery selected from the group consisting of a lithium ion battery, a sodium ion battery, a potassium ion battery, a zinc ion battery, a magnesium ion battery, an aluminum ion battery, and combinations thereof.

[0087]

[0164] In general, in another embodiment, the invention features a method of resynthesizing a cathode material. The method includes subjecting the cathode material to a flash Joule heating process to form a ferromagnetic flash product. The method further includes subjecting the ferromagnetic flash product to a hydrothermal and calcination process to form a resynthesized cathode material. [Brief description of the drawings]

[0088] [Figure 1-1]

[0165] 1A-1F are schematic diagrams and graphs relating to flash recycling of cathode waste: Fig. 1A is a schematic diagram of a flash recycling process of cathode waste, and Figs. 1B-1C are schematic diagrams of conventional hydrometallurgical and pyrometallurgical processes, respectively. [Figure 1-2] FIG. 1D is a graph showing real-time temperature measurements by fitting blackbody radiation from samples during the flash recycling process and enumerating rapid cooling, all completed in less than 0.5 seconds. FIG. 1E is a graph showing the temperature-vapor pressure relationship for various metals contained in the cathode waste. FIG. 1F is a graph showing the magnetic response of the unflashed cathode waste, the ferromagnetic portion of the flash recycled cathode waste (which is about 90% of the product), and the non-ferromagnetic portion of the flash recycled cathode waste (which is about 10% of the product). [Figure 2-1]

[0166] 2A-2B show a scheme of the FJH system: Fig. 2A is an electrical schematic of the FJH system; Fig. 2B is a photograph of the FJH reaction box. [Figure 2-2]

[0166] Figures 2A-2B show a scheme of the FJH system. Figure 2A is an electrical schematic of the FJH system. Figure 2B is a diagram of the FJH reaction box. [Diagram 3]

[0167] 3A-3C show current-time curves during the flash reaction. FIG. 3A is a graph of a new lithium cobalt oxide (LiCoO2) (LCO) cathode material. FIG. 3B is a graph of a new lithium nickel manganese cobalt oxide (LiNixMnyCozO2, commonly referred to as NMCxyz, e.g., NMC811) (NMC) cathode material. FIG. 3C is a graph of cathode waste obtained from a spent LIB. The vertical lines in the current sweep reflect 1000 Hz cycling of the electrical input. [Figure 4]

[0168] Figure 4 shows the spectrum recorded by a spectrometer with 16-channel optical fibers. The wavelengths of these channels range from 1000 nm to 640 nm with equal intervals of 24 nm. Then, fitting of the blackbody radiation (BBR) was used to obtain the temperature at each time point shown in Figure 1D. [Diagram 5]

[0169] 5A-5B show the magnetic response of the cathode material. Figure 5A is a graph of the enlarged hysteresis loops of CW, the non-ferromagnetic portion of flash-recycled CW (fCW non-magnetic) and the ferromagnetic portion of flash-recycled CW (fCW magnetic). Figure 5B is a graph showing the behavior of the hysteresis loops around the onset of fCW magnetic properties. [Figure 6]

[0170] Figures 6A-6D show the magnetic response of the cathode waste and the flash product. Figures 6A-6B are illustrations showing that the cathode waste was not attracted by the bar magnet. Figures 6C-6D show that the flash recycled CW is predominantly ferromagnetic. [Figure 7]

[0171] Figure 7 shows the magnetic response of the reflashed cathode material. The magnetic response is for the ferromagnetic portion of the reflashed recycled cathode waste, which is about 60 wt% of the product, and the non-ferromagnetic portion of the reflashed recycled cathode waste, which is about 40 wt% of the product. The similar magnetization behavior of the ferromagnetic portion of the reflashed recycled cathode waste confirms their effective separation by the same magnet with a field strength of about 5000 Oe. [Figure 8-1]

[0172] Figures 8A-8E show the structure and chemical composition of the reflash recycled product. Figure 8A is the FTIR spectrum of the non-ferromagnetic portion of the flash recycled CW (NMC plus LCO), the ferromagnetic portion of the reflash recycled CW, and the non-ferromagnetic portion of the reflash recycled CW. Figure 8B is the XRD spectrum of the ferromagnetic portion of the reflash recycled CW. Figure 8C is an SEM image of the ferromagnetic portion of the reflash recycled CW. [Figure 8-2] Figure 8D is the elemental mapping of the energy dispersive analysis, and Figure 8E is the corresponding spectrum of the ferromagnetic part of the reflash-recycled CW. [Figure 9]

[0173] 9A-9D show the magnetic response of various cathode materials. FIG. 9A shows the hysteresis loops at room temperature (300 K) for NMC and the ferromagnetic portion of flash-recycled NMC (fNMC magnetic). FIG. 9B shows the behavior of the hysteresis loops around the onset for NMC and fNMC. FIG. 9C shows the hysteresis loops at room temperature (300 K) for LCO and the ferromagnetic portion of flash-recycled LCO (fLCO magnetic). FIG. 9D shows the behavior of the hysteresis loops around the onset for LCO and fLCO. [Figure 10]

[0174] 10A-10B are visual images of the ferromagnetic portion of LCO from approximately 200 mg scale and approximately 800 mg scale, respectively.

[0175] 10C-10D are visual images of ferromagnetic portions of NMC811 from approximately 200 mg scale and approximately 800 mg scale, respectively. [Figure 11-1]

[0176] Figures 11A-11G show the recovery efficiency of various cathode materials. Figure 11A is a graph showing the recovery of Li and Co in the ferromagnetic part of the flash recycled LCO product after a single flash (1.0=100%). The number of samples is N=5, and the bars show the standard deviation between runs. Figure 11B is a graph showing a comparison of the recovery of Li and Co by different recycling methods, together with references. Figure 11C is a graph showing the recovery of Li, Co, Ni and Mn in the ferromagnetic part of flashed NMC811. N=5. Figure 11D is a graph showing the recovery of Li, Co, Ni and Mn in the ferromagnetic part of flashed commercial cathode waste (fCW) from spent LIBs. N=5. For Figures 11C-11D, the yields are compared against the content of metals recovered by aqueous acid digestion, and therefore may exceed 1.0 in some cases. [Figure 11-2] 11E-11G are radar plots reporting the recovery of various metals from cathode waste using flash recycling and traditional hydrometallurgical and pyrometallurgical methods, respectively. For FIG. 11E, the darker shading is recovery after a single flash and the lighter shading is recovery after a second flash. [Figure 12]

[0177] 12A-12C are radar plots reporting a comparison of the recovery of various metals from LCO using flash recycling and traditional hydrometallurgical and pyrometallurgical methods, respectively. The structural retention factor R value is 7.77 / 3.03=2.57 for LCO.

[0178] 12D-12F are radar plots reporting a comparison of the recovery of various metals from NMC using flash recycling and traditional hydrometallurgical and pyrometallurgical methods, respectively. The structural retention factor R value is 0.29 / 0.57=0.51 for NMC. [Figure 13-1]

[0179] Figures 13A-13J show the structure and chemical composition of the flash recycled product. Figure 13A is a high-resolution XPS spectrum of Co 2p in the surface and subsurface regions of the ferromagnetic part of the flash recycled CW (fCW). Figure 13B is a graph showing the elemental ratios at different depths of the ferromagnetic part of the fCW (LCO+NMC). The spectra were acquired at different depths after surface etching. Fluorides from the electrolyte were deposited during the CEI formation in the spent LIB. Figure 13C is a schematic diagram of the ferromagnetic part of the fCW particle with a hierarchical structure. [Figure 13-2] Figure 13D is an HAADF image and corresponding energy dispersive analysis elemental mapping of the ferromagnetic part of fLCO. Figure 13E shows the atomistic structures of partially delithiated LixCoO2 before flash recycling, and the high-quality LiCoO2, Co3O4 and CoO obtained after flash recycling. The right panel demonstrates the magnetization of Co3O4 by plotting the difference between the spin density distributions of the spin-up and spin-down configurations at the maximum magnetic moment of 0.02e- / Å3, about 70 emu / g. [Figure 13-3] Figure 13F is an HR-TEM image of R-LCO reporting the presence of layered structures at the surface. The inset in Figure 13F is the corresponding FFT pattern. Figure 13G is an atomic resolution HAADF-STEM image of R-LCO. [Figure 13-4] FIG. 13H is a HAADF image of R-CW and the corresponding energy dispersive analysis elemental mapping. [Figure 13-5] FIG. 13I is an image of a Li-ion permeable partially graphitized amorphous carbon structure at the end of 9 ns annealing at 2500 K, where the lines shown are potential Li-ion trajectories. [Figure 13-6] FIG. 13J is a graph showing the electrochemical performance of spent CW, resynthesized cathode material and fresh LCO in the prepared half-cell. The rate for testing is 0.2C. [Figure 14-1]

[0180] Figures 14A-14E show the chemical composition of ferromagnetic flash recycled CW (fCW) from a mixture of LCO and NMC contained in a used commercial laptop computer battery. Figure 14A shows the full scan XPS result of the ferromagnetic fCW. Figures 14B-14E show the high resolution XPS spectra of C 1s, O 1s, F 1s, and Li 1s at the surface and subsurface regions of the ferromagnetic fCW, respectively. After surface etching, the spectra were acquired at different depths. [Figure 14-2] Figures 14A-14E show the chemical composition of ferromagnetic flash recycled CW (fCW) from a mixture of LCO and NMC contained in a used commercial laptop computer battery. Figure 14A shows the full scan XPS result of the ferromagnetic fCW. Figures 14B-14E show the high resolution XPS spectra of C 1s, O 1s, F 1s, and Li 1s at the surface and subsurface regions of the ferromagnetic fCW, respectively. After surface etching, the spectra were acquired at different depths. [Figure 15-1]

[0181] Figures 15A-15G show the chemical composition of CW from a mixture of LCO and NMC obtained from a used commercial laptop computer battery. Figure 15A shows the full scan XPS results of the CW. Figures 15B-15F show the high resolution XPS spectra of C 1s, Co 2p, F 1s, Li 1s, and O 1s at the surface and subsurface regions of the CW, respectively. After surface etching, the spectra were acquired at different depths. Figure 15G shows the elemental ratios at different depths of the CW. [Figure 15-2]

[0181] Figures 15A-15G show the chemical composition of CW from a mixture of LCO and NMC obtained from a used commercial laptop computer battery. Figure 15A shows the full scan XPS results of the CW. Figures 15B-15F show the high resolution XPS spectra of C 1s, Co 2p, F 1s, Li 1s, and O 1s at the surface and subsurface regions of the CW, respectively. The spectra were acquired at different depths after surface etching. Figure 15G shows the elemental ratios at different depths of the CW. [Figure 16-1]

[0182] Figures 16A-16F show the chemical composition of the ferromagnetic portion of flash recycled LCO (fLCO) from 0 nm to 500 nm. Figure 16A shows the full scan XPS results of ferromagnetic fLCO. Figures 16B-16E show the high resolution XPS spectra of C 1s, Co 2p, Li 1s, and O 1s at the surface and subsurface regions of fLCO, respectively. After surface etching, the spectra were acquired at different depths. Figure 16F shows the elemental ratios at different depths of ferromagnetic fLCO. [Figure 16-2]

[0182] Figures 16A-16F show the chemical composition of the ferromagnetic portion of flash recycled LCO (fLCO) from 0 nm to 500 nm. Figure 16A shows the full scan XPS results of ferromagnetic fLCO. Figures 16B-16E show the high resolution XPS spectra of C 1s, Co 2p, Li 1s, and O 1s at the surface and subsurface regions of fLCO, respectively. After surface etching, the spectra were acquired at different depths. Figure 16F shows the elemental ratios at different depths of ferromagnetic fLCO. [Figure 17-1]

[0183] Figures 17A-17F show the chemical composition of the ferromagnetic portion of flash recycled LCO (fLCO) from 0 nm to 100 nm. Figure 17A shows the full scan XPS results of ferromagnetic fLCO. Figures 17B-17E show the high resolution XPS spectra of C 1s, Co 2p, Li 1s, and O 1s at the surface and subsurface regions of flash LCO, respectively. After surface etching, the spectra were acquired at different depths. Figure 17F shows the elemental ratios at different depths of ferromagnetic fLCO. [Figure 17-2]

[0183] Figures 17A-17F show the chemical composition of the ferromagnetic portion of flash recycled LCO (fLCO) from 0 nm to 100 nm. Figure 17A shows the full scan XPS results of ferromagnetic fLCO. Figures 17B-17E show the high resolution XPS spectra of C 1s, Co 2p, Li 1s, and O 1s at the surface and subsurface regions of flash LCO, respectively. The spectra were acquired at different depths after surface etching. Figure 17F shows the elemental ratios at different depths of ferromagnetic fLCO. [Figure 18-1]

[0184] Figures 18A-18H show the chemical composition of the ferromagnetic portion (fNMC) from 0 nm to 500 nm of flash recycled NMC. Figure 18A shows the full scan XPS results of the ferromagnetic fNMC. Figures 18B-18G show the high resolution XPS spectra of C 1s, Co 2p, Li 1s, O 1s, Ni 2p and Mn 2p at the surface and subsurface regions of the fNMC, respectively. After surface etching, the spectra were acquired at different depths. Figure 18H shows the elemental ratios at different depths of the ferromagnetic fNMC. [Figure 18-2]

[0184] Figures 18A-18H show the chemical composition of ferromagnetic portion (fNMC) from 0 nm to 500 nm flash recycled NMC. Figure 18A shows the full scan XPS result of ferromagnetic fNMC. Figures 18B-18G show the high resolution XPS spectra of C 1s, Co 2p, Li 1s, O 1s, Ni 2p and Mn 2p at the surface and subsurface regions of fNMC, respectively. After surface etching, the spectra were acquired at different depths. Figure 18H shows the elemental ratios at different depths of ferromagnetic fNMC. [Figure 18-3]

[0184] Figures 18A-18H show the chemical composition of ferromagnetic portion (fNMC) from 0 nm to 500 nm flash recycled NMC. Figure 18A shows the full scan XPS result of ferromagnetic fNMC. Figures 18B-18G show the high resolution XPS spectra of C 1s, Co 2p, Li 1s, O 1s, Ni 2p and Mn 2p at the surface and subsurface regions of fNMC, respectively. After surface etching, the spectra were acquired at different depths. Figure 18H shows the elemental ratios at different depths of ferromagnetic fNMC. [Figure 19-1]

[0185] Figures 19A-19H show the chemical composition of ferromagnetic portion (fNMC) from 0 nm to 100 nm flash recycled NMC. Figure 19A shows the full scan XPS results of ferromagnetic fNMC. Figures 19B-19G show the high resolution XPS spectra of C 1s, Co 2p, Li 1s, O 1s, Ni 2p and Mn 2p at the surface and subsurface regions of fNMC, respectively. After surface etching, the spectra were acquired at different depths. Figure 19H shows the elemental ratios at different depths of ferromagnetic fNMC. [Figure 19-2]

[0185] Figures 19A-19H show the chemical composition of ferromagnetic portion (fNMC) from 0 nm to 100 nm flash recycled NMC. Figure 19A shows the full scan XPS results of ferromagnetic fNMC. Figures 19B-19G show the high resolution XPS spectra of C 1s, Co 2p, Li 1s, O 1s, Ni 2p and Mn 2p at the surface and subsurface regions of fNMC, respectively. After surface etching, the spectra were acquired at different depths. Figure 19H shows the elemental ratios at different depths of ferromagnetic fNMC. [Figure 19-3]

[0185] Figures 19A-19H show the chemical composition of ferromagnetic portion (fNMC) from 0 nm to 100 nm flash recycled NMC. Figure 19A shows the full scan XPS results of ferromagnetic fNMC. Figures 19B-19G show the high resolution XPS spectra of C 1s, Co 2p, Li 1s, O 1s, Ni 2p and Mn 2p at the surface and subsurface regions of fNMC, respectively. After surface etching, the spectra were acquired at different depths. Figure 19H shows the elemental ratios at different depths of ferromagnetic fNMC. [Figure 20]

[0186] FIG. 20A shows the X-ray diffraction spectra of CW, ferromagnetic fCW, and non-ferromagnetic fCW.

[0187] FIG. 20B shows an expanded X-ray diffraction spectrum at the low angle range indicated by the dashed rectangle in FIG. 20A. [Figure 21]

[0188] FIG. 21A shows the X-ray diffraction spectra of new lithium cobalt oxide (LCO), ferromagnetic fLCO, and non-ferromagnetic fLCO.

[0189] FIG. 21B shows an expanded X-ray diffraction spectrum at the low angle range indicated by the dashed rectangle in FIG. 21A. [Figure 22]

[0190] FIG. 22A shows the X-ray diffraction spectra of the new lithium nickel-manganese-cobalt oxide and ferromagnetic fNMC.

[0191] FIG. 22B shows an expanded X-ray diffraction spectrum at the low angle range indicated by the dashed rectangle in FIG. 22A. [Figure 23-1]

[0192] FIG. 23A shows the FTIR spectra of the CW and fCW ferromagnetic portions.

[0193] Figure 23B shows the size distribution of the ferromagnetic fraction of the starting CW and fCW particles of the material shown in Figure 23A. The number of particles is N=100. [Figure 23-2]

[0194] 23C-23D show SEM images of the fCW ferromagnetic portion and the starting CW grains, respectively, of the material shown in FIG. 23A. [Figure 24]

[0195] 24A-24D are images obtained from a mixture of LCO and NMC. FIG. 24A is an SEM image of a CW from a mixture of LCO and NMC before flash recycling. FIG. 24B is a higher resolution SEM image of the CW before flash recycling. FIG. 24C is an SEM image of the ferromagnetic portion of the fCW. FIG. 24D is a higher resolution SEM image of the ferromagnetic portion of the fCW. [Figure 25-1]

[0196] Figures 25A-25F are images obtained from the LCO. Figure 25A shows an SEM image of the LCO before flash recycling. Figure 25B shows a higher resolution SEM image of the LCO before flash recycling. Figure 25C shows an SEM image of the ferromagnetic portion of the fLCO. Figure 25D shows a higher resolution SEM image of the ferromagnetic portion of the fLCO. [Figure 25-2] Figure 25E shows the particle size distribution of the ferromagnetic fraction of the new LCO and fLCO particles. Number of samples N=100. Figure 25F shows the FTIR spectra of LCO and ferromagnetic fLCO. [Figure 26-1]

[0197] Figures 26A-26F are images obtained from the NMC. Figure 26A shows an SEM image of the NMC before flash recycling. Figure 26B shows a higher resolution SEM image of the NMC before flash recycling. Figure 26C shows an SEM image of the ferromagnetic portion of the fNMC. Figure 26D shows a higher resolution SEM image of the ferromagnetic portion of the flash NMC. [Figure 26-2] Figure 26E shows the particle size distribution of the ferromagnetic portion of NMC and fNMC particles. Number of samples N=100. Figure 26F shows the FTIR spectra of NMC and ferromagnetic fNMC. [Figure 27-1]

[0198] Figures 27A-27E show FIB-SEM images of the carbon coated structures. Figure 27A is a top-down SEM image showing the ferromagnetic fCW particles after FIB cutting. Figures 27B-27C are cross-sectional SEM images showing the boundary between the surface carbon coating and the underlying ferromagnetic fCW particles. A dashed line is used to clarify the boundary. [Figure 27-2] Figure 27D is an SEM image of the cross section of a ferromagnetic fCW particle after FIB cutting and the corresponding elemental distribution of O, C, and Co. Figure 27E is an SEM image of the top view of a ferromagnetic fCW particle after FIB cutting and the corresponding elemental distribution of O, C, and Co. [Figure 28]

[0199] 28A-28B are fLCO magnetic and LCO schemes, respectively, showing the hierarchical structure of flash cathode particles. [Figure 29-1]

[0200] Figures 29A-29H are TEM images of the ferromagnetic portion of the fLCO particles, Figures 29A-29B are HR-TEM images of the ferromagnetic fLCO particles, and Figures 29C-29D are Fast Fourier Transform results of the ferromagnetic fLCO particles. [Figure 29-2] Figures 29E-29F are HR-TEM images of the new LCO particles, and Figures 29F-29G are SAED patterns of the new LCO particles. [Diagram 30]

[0201] FIG. 30 is a graph showing the energy trends versus phase segregation for a partially delithiated CW material. [Figure 31-1]

[0202] FIG. 31A is an X-ray diffraction spectrum of a commercial cathode material in the charged and discharged states. [Figure 31-2]

[0203] 31B-31C are expanded X-ray diffraction spectra at different angle ranges indicated by the left and right dashed rectangles, respectively, in FIG. 31A. [Diagram 32]

[0204] Figure 32 shows the characterization of the Li source with curves for the LiOH·H2O reactant and the recovered Li material, respectively. The heating rate was set at 10 °C / min and the N2 flow was maintained at 80 mL / min throughout the run. [Figure 33-1]

[0205] Figures 33A-33E show the characterization of the resynthesis conditions: Figure 33A shows an Ellingham diagram of the relevant reactions. [Figure 33-2]Figure 33B shows the XRD results of the resynthesized cathode materials using calcination temperatures of 400 °C (R-CW-400) and 500 °C (R-CW-500). Figures 33C-33E show the thermogravimetric curves and corresponding differential scanning calorimetry analysis of the ferromagnetic parts of LCO and fLCO. The heating rate was set at 10 °C / min and the air flow was maintained at 80 mL / min throughout the run. In Figure 33E, the temperature was held at 500 °C for 30 min to test the thermal stability at 500 °C. [Figure 33-3] Figures 33C-33E are thermogravimetric curves and corresponding differential scanning calorimetry analyses of the ferromagnetic portions of LCO and fLCO. The heating rate was set at 10 °C / min and the air flow was maintained at 80 mL / min throughout the run. In Figure 33E, to test the thermal stability at 500 °C, the temperature was held at 500 °C for 30 min. [Figure 34-1]

[0206] Figures 34A-34I show the morphology of the resynthesized cathode. Figures 34A-34C are SEM images of R-CW reporting a uniform carbon coating and layered structure. [Figure 34-2] Figures 34D-34E are HR-TEM images of R-LCO particles reporting the layered structure of the recovered cathode, and Figure 34F is a HAADF-STEM image of an R-LCO particle. [Figure 34-3] 34G-34I are elemental mappings of the energy dispersive analysis of the corresponding R-LCO particles. [Figure 35-1]

[0207] Figures 35A-35E show the characterization of the resynthesized cathode. Figure 35A shows the FTIR spectra of the cathode waste and the resynthesized cathode material (R-CW). Figure 35B shows the FTIR spectra of the LCO and the resynthesized cathode material (R-LCO). [Figure 35-2] Figure 35C shows the room temperature (300 K) hysteresis loops of the flash recycled NMC ferromagnetic part (fCW magnetic), flash CW after hydrothermal reaction (post-hydrothermal) and resynthesized cathode material (R-CW). Figure 35D shows the behavior of the hysteresis loops around the origin for these three samples. [Figure 35-3]FIG. 35E shows the electrochemical performance of fresh NMC (NMC) in the prepared half-cell. The rate for testing was 0.2C. [Diagram 36]

[0208] Figures 36A-36C show the morphology of the carbon coating structure: Figure 36A is a TEM image of an R-CW particle, and Figures 36B-36C are HR-TEM images of an R-CW particle reporting the amorphous character of the carbon coating at the surface. [Figure 37-1]

[0209] Figures 37A-37J show the elemental distribution of the resynthesized cathode material. Figure 37A is an energy dispersive X-ray spectrum of the R-CW particle. Figure 37B is an HAADF-STEM image of the R-CW particle. Figure 37C is a BF-STEM image of the R-CW particle. Figures 37D-37J are the corresponding elemental mappings of the R-CW particle. [Figure 37-2] 37D-37J are the corresponding elemental mappings of the R-CW grains. [Figure 38-1]

[0210] Figures 38A-38D show the crystal structure of the resynthesized cathode material. Figure 38A is an HR-TEM image of R-LCO reporting the presence of layered structures at the surface of the cathode particles. Figure 38B is the corresponding FFT pattern of the R-LCO shown in Figure 38A. [Figure 38-2] 38C-38D are atomic resolution HAADF-STEM images of R-LCO reporting the presence of layered structures at the surface of the cathode particles. [Figure 39]

[0211] 39A-39E show the configurations of the carbon crust after annealing at various temperatures (700K, 1000K, 1500K, 2000K, and 2500K, respectively) for 9 ns. [Figure 40-1]

[0212] Figures 40A-40D show the diffusion barrier of Li+ in various structures within an amorphous carbon shell. Figure 40A shows the edge of an unpassivated monolayer of graphene. Figure 40B shows the edge of an unpassivated bilayer of graphene. [Figure 40-2]FIG. 40C shows the reconstructed di-vacancy forming a 5-8-5 defect (the largest barrier corresponds to diffusion through the 8-ring defect to the other side of the face; steps 7-10). FIG. 40D shows that diffusion across the reconstructed edge of bilayer graphene exhibits a barrier nearly identical to that for diffusion into planar graphene, around 0.34 eV. [Figure 41-1]

[0213] Figures 41A-41F show economic and environmental analyses of pyrometallurgical (pyro), hydrometallurgical (hydro), and flash recycling processes. Figure 41A is a scheme of a life cycle analysis of a Li-ion battery showing that flashing is the more direct route to recycling. [Figure 41-2] Figure 41B shows the recycling revenue and recycling cost per kilogram of cathode resynthesized by various methods. Figure 41C shows the net profit per kilogram of cathode resynthesized by various methods. [Figure 41-3] FIG. 41D shows the total energy consumption of recomposing 1 kg of cathode material using pyrometallurgy, hydrometallurgy, and flash recycling methods. As a comparison, the energy cost from mining unprocessed ore is shown. FIG. 41E shows the GHG emissions in recomposing 1 kg of cathode material using pyrometallurgy, hydrometallurgy, and flash recycling methods. As a comparison, the GHG emissions using unprocessed ore are shown. [Figure 41-4] FIG. 41F shows the net profit per kilogram of various cathodes resynthesized by pyrometallurgical, hydrometallurgical, and flash recycling methods. [Figure 42-1]

[0214] FIG. 42A is a scheme of a life cycle analysis of a lithium-ion battery. [Figure 42-2]

[0215] FIG. 42B is a simplified flow chart of a pyrometallurgical process. [Figure 42-3]

[0216] FIG. 42C is a simplified flow chart of a hydrometallurgical process. [Figure 42-4]

[0217] FIG. 42D is a simplified flow chart of a flash recycling method. [Figure 43-1]

[0218] Figures 43A-43B show a scheme of the FJH system: Figure 43A is an electrical schematic diagram of the FJH system. [Figure 43-2] Figure 43B is a diagram of the large FJH reaction box. [Figure 44-1]

[0219] Figures 44A-44C show flash recycling of a graphite anode, and Figures 44A-44B are schematic diagrams of flash recycling of anode waste and the effect of resistance-dependent Joule heating in a multiphase system, respectively. [Figure 44-2] FIG. 44C is the corresponding current-time curve during the flash recycling process. [Diagram 45]

[0220] 45A-45B show the general procedure of the conventional high temperature calcination method and the real-time temperature curves from the sample during the flash recycling process, respectively. [Diagram 46]

[0221] Figures 46A-46D show the thermal stability results of various anode materials. Figures 46A-46B are the TGA and DSC results of anode waste (AW), calcined anode waste (cAW), flash anode waste (fAW), and graphite, respectively. Figures 46C-46D are the TGA and DSC results of AW, fAW100V, fAW120V, and fAW120V x 2, respectively. TGA and DSC data were collected from 25 to 1000 °C under air. The heating rate was set at 10 °C / min and the air flow was maintained at 80 mL / min throughout the run. [Figure 47]

[0222] Figure 47 shows the results of thermal stability tests by TGA: remaining mass fraction of various treated graphite anode materials at T = 773K. [Figure 48-1]

[0223] 48A-48D are visual images of anode waste, calcined anode waste, flash anode waste (200 mg / batch), and flash anode waste (1 g / batch), respectively. [Figure 48-2]

[0224] Figures 48E-48F are the TGA and DSC results of AW and fAW on the gram scale, respectively. TGA and DSC data were collected from 25 to 1000°C under air. The heating rate was set at 10°C / min and the air flow was maintained at 80 mL / min throughout the run. [Figure 49]

[0225] Figure 49 shows the thermal stability test by TGA: remaining mass fraction of various treated graphite anode materials at T = 1273K. [Figure 50]

[0226] FIG. 50 shows the crystal structures of cAW, fAW, and AW. [Figure 51]

[0227] 51A-51B are high-resolution XRD spectra of various anode materials (AW, cAW, and fAW). [Figure 52]

[0228] 52A-52C are high-resolution XRD spectra of fAW (gram scale). [Figure 53]

[0229] FIG. 53 shows the surface composition of fAW and AW. [Figure 54]

[0230] FIG. 54 shows the surface composition of cAW. [Figure 55-1]

[0231] Figures 55A, 55C, and 55E show the chemical composition of the anode materials from 0 nm (surface) to a depth of 450 nm for AW, fAW, and cAW, respectively. After surface etching, the spectra were acquired at different depths.

[0232] 55B, 55D, and 55F show the elemental distribution of AW, fAW, and cAW particles, respectively, in the 0-500 nm subsurface region. [Figure 55-2]

[0231] Figures 55A, 55C, and 55E show the chemical composition of anode materials from 0 nm (surface) to a depth of 450 nm for AW, fAW, and cAW, respectively. After surface etching, the spectra were acquired at different depths.

[0232] Figures 55B, 55D, and 55F show the elemental distribution of AW, fAW, and cAW particulates, respectively, in the 0-500 nm subsurface region. [Figure 56]

[0233] Figure 56 shows the UV-vis spectra of aqueous leaching solutions of fAW and AW. The visual images show yellowish and clear solutions obtained from AW and fAW, respectively. [Figure 57-1]

[0234] Figures 57A-57I are SEM images of various anode materials. Figures 57A-57C are AW and Figures 57D-57F are fAW. [Figure 57-2] Figures 57G to 57I are cAW.

[0235] Figures 57J-57K are statistical studies showing the size of AW, fAW, and cAW, respectively. For each, the number of samples is N=50. The particle size distribution results show that AW, fAW, and cAW have similar average particle sizes. [Figure 58]

[0236] Figures 58A-58D are images of the anode waste. Figures 58A-58B are TEM images and Figures 58C-58D are HR-TEM images. The average thickness of the SEI around the graphite particles is about 145 nm. Under the SEI region, the graphite crystal lattice can be observed as shown in Figure 16c. Furthermore, there are many small crystals embedded within the SEI, which is consistent with the mosaic model of the SEI structure. [Figure 59]

[0237] Figures 59A-59D are images of the flash anode waste. Figures 59A-59B are TEM images; Figures 59C-59D are HR-TEM images. The decomposition of the SEI and the formation of graphene shells and nanoparticles, such as LiF and Co3O4, can be observed, which is consistent with the elemental distribution and XRD spectrum results. The average thickness of the layer also decreases from about 145 nm to about 65 nm. This SEI-derived layer is composed of graphene layers and embedded nanoparticles, indicating that the flash method can be an effective method to decompose the SEI and then convert it into a protective graphene layer. [Figure 60]

[0238] Figure 60 shows the STEM images and corresponding element distribution of the anode waste. The scale bar is the same for all images. Metal elements, such as Co (~0.2 at%), are uniformly distributed in the anode SEI in the case of pristine AW, which may be due to the dissolution and transport of transition metals from the cathode side and may be trapped in the SEI at the anode side. [Figure 61]

[0239] FIG. 61 shows STEM images of fAW particles and the results of their respective elemental mapping. [Figure 62-1]

[0240] Figures 62A-62E show metal ion leaching tests. Figure 62A shows the recovery efficiency and excess yield Y / Y0 of flash anode waste with HCl at different concentrations. The number of samples is N=3, and the bars show the standard deviation between runs, and so on. Figure 62B shows the recovery efficiency and excess yield Y / Y0 of various metal ions of flash anode waste with 0.1M HCl. Figure 62C shows the recovery efficiency and excess yield Y / Y0 of total metal ions of calcined anode waste with HCl at different concentrations. Figure 62D shows the recovery efficiency and excess yield Y / Y0 of total metal ions of flash anode waste after TGA treatment with HCl at different concentrations. [Figure 62-2] FIG. 62E shows the total amount of metal ions and the excess yield Y / Y0 of various treated anode wastes with concentrated hydrochloric acid. [Figure 63]

[0241] Figures 63A-63B are the TGA and DSC results of AW, fAW-W, and AW-W, respectively. TGA and DSC data were collected from 25 to 1000 °C under air. The heating rate was set at 10 °C / min and the air flow was maintained at 80 mL / min throughout the run. fAW-W represents fAW after rinsing with 0.1 M HCl to recollect the useful metal ions. The same is true for other anode materials. [Figure 64]

[0242] Figures 64A to 64C are images of fAW-W. Figure 64A is a TEM image of fAW-W, and Figures 64B to 64C are HR-TEM images of fAW-W.

[0243] Figure 64D is the corresponding FFT pattern along the fAW-W 0002 zone axis shown in Figures 64A-64C. The absence of embedded nanoparticles indicates that post-treatment with dilute acid can be used to effectively collect the useful metals. There is also a unique set of 6x diffraction patterns reflecting the well-graphitized structure of the anodic particles. [Figure 65]

[0244] Figure 65 shows the voltage profiles of the first cycle of AW, cAW, fAW, and graphite at 0.05 C. The areal capacity is about 3.0 mAh / cm2. [Figure 66]

[0245] Figures 66A-66C show the voltage profiles of graphite and fAW (Figure 66A), cAW (Figure 66B) and AW (Figure 66C) at different rates. The areal capacity is about 2.0 mAh / cm2. [Figure 67]

[0246] Figure 67 shows the rate performance of AW, cAW, fAW, and graphite. [Figure 68-1]

[0247] 68A-68C show the preparation of synthetic graphite, the flash recycling method, and the high temperature calcination method, respectively. [Figure 68-2]

[0247] Figures 68A-68C show the preparation of synthetic graphite, the flash recycling method, and the high temperature calcination method, respectively. [Figure 69-1]

[0248] 69A-69C show the GHG emissions, water consumption, and total energy consumption in producing 1 kg of anode material with the flash recycling method (FLASH), the high temperature calcination method (HTC), and 1 kg of synthetic graphite, respectively. [Figure 69-2]

[0249] 69D-69E show the costs and net benefits for preparing 1 kg of synthetic graphite, 1 kg of anode material by the flash recycling method (Flash) and the high temperature calcination method (HTC). [Figure 70]

[0250] FIG. 70 shows that the weight percentages of Li, Co, Ni and Mn can be collected from a cell containing a quartz tube, a graphite spacer and a copper wool electrode but without any sample (ie, the blank group). [Figure 71]

[0251] FIG. 71 shows the total amount of Li and Co in a 1.00 g sample. [Figure 72]

[0252] 72A-72B show the recovery efficiencies of (a) Li and (b) Co from LCO and flash LCO in HCl solutions at different concentrations, respectively. [Figure 73]

[0253] FIG. 73 shows the distribution of Li and Co from LCO and flash LCO after dissolution in 0.1 M HCl solution and rinsing from the quartz tube, graphite spacer, and copper wool electrode. [Figure 74]

[0254] Figure 74 shows the total amounts of Li, Co, Ni and Mn in a 1.00 g sample: (left bar) before flushing; (right bar) after flushing. [Figure 75]

[0255] 75A-75D show the recovery efficiencies of (a) Li, (b) Co, (c) Ni, and (d) Mn from NMC and flash NMC in HCl solutions at different concentrations, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0089]

[0256] The present invention relates to flash recycling of batteries such as lithium-ion batteries, other metal (sodium, potassium, zinc, magnesium, and aluminum) ion batteries, metal batteries, batteries with all metal oxide cathodes, and batteries with all graphite-containing anodes, including a solvent-free and water-free flash joule heating (FJH) method performed in combination with magnetic separation to recover lithium, cobalt, nickel, and manganese. The combination of the solvent- and water-free FJH method with magnetic separation can be utilized to recycle spent batteries, i.e., spent lithium-ion batteries (LIBs), other spent metal-ion batteries, and spent metal batteries. The FJH method disclosed and discussed herein will focus on lithium-ion batteries (LIBs). Similar methods can be applied to other metal-ion batteries (and their cathodes and anodes), such as sodium, potassium, zinc, magnesium, and aluminum ion batteries, as well as the anodes and cathodes of metal batteries, including batteries without an anode (which means there is no excess anode metal) and metal-oxygen and metal-air batteries.

[0090]

[0257] This method is extremely rapid and preserves the morphology of the particles (Figure 1A). Conventional recycling strategies for recovering useful metals contained in spent cathode waste (CW) include pyrometallurgy and hydrometallurgy [Tran 2018], which require harsh conditions, such as extreme furnace temperatures above 1400 °C [Lv 2018; Li 2016] or corrosive agents such as hydrochloric acid, nitric acid, and sulfuric acid (Figures 1B-1C) [Chagnes 2013]. In addition, these methods require high energy, generate significant greenhouse gases (GHG) and secondary waste, and lead to the decomposition of materials to their elemental or ionic solutions during recycling, thereby increasing the cost of recycling them back to the cathode morphology [Xu 2020]. In the flash method of the present invention, the hierarchical cathode morphology is preserved while other components of the CW, such as the catholyte interphase (CEI), decompose (Figure 1A).

[0091] Flash recycling process for cathode materials.

[0258] Flash recycling of LIBs is an environmentally cleaner way to regenerate metals in secondary batteries. The method preserves the 3D layered structure of the cathode and provides efficient reuse of elemental inventory. The rapid process also results in a convenient carbon coating on the recycled cathode particles that stabilizes the overall structure of the cathode while allowing Li-ion transport, thereby providing recycled batteries with superior performance over new batteries. The FJH process can be industrially scaled to multi-ton scale per facility [Universal Matter 2021], thus enabling ease of manufacturing while minimizing reliance on newly mined metal ores for LIB production.

[0092]

[0259] In the flash recycling process, a mixture of cathode material and conductive additive (e.g., about 10 wt%, e.g., carbon black) or graphite (e.g., about 20 wt%) from used anodes is slightly compressed inside a quartz tube between two electrodes. [Luong 2020; Chen 2021]. The carbon additive is used to increase the conductivity of the mixture. A capacitor bank in the circuit can be used to provide electrical heat energy to the reactants for about 300 ms. See Figures 2A-2B.

[0093]

[0260] For example, electrodes were collected by discharging a used Li-ion battery in the circuit until the voltage was less than 2.5 V, and then manually dismantling the used battery. The cathode waste was directly removed from the used electrode before it was used. Unless otherwise specified, the cathode material and conductive additive (10 wt% carbon black or 20 wt% used anode graphite) were mixed homogeneously by grinding with a mortar and pestle for about 10 min. The reactants were loaded into a quartz tube with an inner diameter of 4 or 8 mm. The loading mass in the 4 and 8 mm tubes was 200 mg and 800 mg, respectively. A graphite rod and copper wool were used as electrodes and spacers, respectively. They were used to compress the reactants as shown in Figure 1A. In the quartz tube, the graphite rod was in contact with the sample. Electrical energy was provided by a capacitor bank in the circuit with a total capacitance of 60 mF (4 mm tube) or 132 mF (8 mm tube). The capacitor bank was charged by a DC power supply that could reach 400 V. The duration of the flash was controlled by an Arduino controller relay in the circuit acting as a high-speed switch.

[0094]

[0261] Various cathode materials, a combination of LCO and NMC cathodes, were also used to demonstrate the versatility of the flash recycling method. Tables I-II show the flash conditions for different cathode materials in small and large batches, respectively.

[0095] [Table 1]

[0096] [Table 2]

[0097]

[0262] After the FJH reaction, the reaction was allowed to cool for 3 min, and then the ferromagnetic portion of the flashed product was immediately separated using a commercial bar magnet with a magnetic field strength of about 5000 Oe. The mass ratio of the ferromagnetic portion was about 90 wt%, and the mass ratio of the non-magnetic portion was about 10 wt%. The remaining about 10 wt% of the flashed product that was not captured by the magnet was collected and combined with a small portion from other FJH runs and reflashed. The flash conditions were the same as those used for the primary flash. For the reflash experiment, a small batch experiment was used as a demonstration, whereby about 60 wt% of the reflashed product could be magnetically recovered.

[0098]

[0263] In this flash recycling process, with a voltage of 150 V and a resistance of 3 Ω, the current passing through the sample is recorded to reach about 40 A with a discharge time of about 300 ms (Figures 3A-3C). The temperature can be measured via a 16-channel fiber optic spectrometer by fitting the blackbody radiation (Figure 4). The temperature was estimated to be about 2500 K. The ultrafast cooling rate was also measured, about 1.2 × 10 4 The thermal conductivity of the cathode is recorded in K / s (Figure 1D). While pyrometallurgical methods cause the loss of the more volatile Li (Figure 1B) and irreversible collapse of the cathode structure [Lv 2018], the instantaneous high temperatures in flash recycling avoid the loss of Li and preserve the grain morphology and the 3D layered structure of the cathode.

[0099]

[0264] Used LIBs, LCO (LiCoO2) and NMC (LiNi x Mn y Co z O2, usually referred to as NMCxyz, e.g. NMC 811CW from a flash recycled product was tested. The CW consisted of a mixture of LCO and NMC. The flash recycled product contained a mixture of ferromagnetic (~90 wt%) and non-ferromagnetic (~10 wt%) fractions (Figures 1A, 1F, and 5A-5B). The ferromagnetic fraction of the flash recycled product showed a sharp response to an external magnetic field, whereas the reactants showed no ferromagnetic response. This magnetization was strong enough to ensure effective separation of the ferromagnetic fraction by a normal hand-held magnet with a field strength of ~5000 Oe.

[0100]

[0265] A simple magnet was used to extract the desired ferromagnetic fraction (Figures 1A and 6A-6D). The extracted ferromagnetic product contained Li and transition metals, where Li was successfully extracted with the magnet since it is closely associated with ferromagnetic metals.

[0101]

[0266] Additionally, the remaining 10% non-ferromagnetic fraction may be reflashed as shown in Figures 7 and 8A-8E. This process works with LCO, NMC and mixtures thereof, as found in commercial CWs recovered from spent LIBs from old laptop computer batteries (Figures 9A-9D).

[0102]

[0267] As shown in Figures 1F and 5A-5B, the ferromagnetic part of the flashed cathode waste (fCW magnetic, orange curve) had a sharp response to an external magnetic field (about 10 emu / g at 1900 Oe). The magnetic moment reaches saturation (about 17 emu / g) at 8000 Oe. This magnetization was strong enough to ensure effective separation of the ferromagnetic part by a regular hand-held magnet with a magnetic field strength of about 5000 Oe. The coercive force was small, calculated from Figure 5B, indicating that the magnetization of the material could easily reverse direction without significant energy dissipation (hysteresis losses). In contrast, fCW nonmagnetic and intrinsic CW showed a weak magnetic response to an external magnetic field, which are paramagnetic and diamagnetic materials, respectively. Therefore, a regular magnet can be used to capture the ferromagnetic part of the flashed recycled cathode waste to recover the metals Co, Li, Ni, Mn from used batteries. Li, although non-magnetic, was captured by the fine particles of the ferromagnetic portion.

[0103]

[0268] Regarding the re-flashing of the non-magnetic fraction, the remaining 10 wt% of the flash product that was not captured by the magnet may be combined with small fractions from other FJH runs to be re-flashed, and the flash conditions were the same as those used for the flash recycling of the cathode waste. Thereby, about 60 wt% of this could be magnetically recovered. Moreover, it behaves similarly to the initially flashed magnetic fraction. ICP-OES results show excellent recoveries from the re-flashing process, including Li (79%), Co (77%), Ni (73%) and Mn (84%). As a result, further use of the remaining 10 wt% of the non-magnetic fraction in the re-flashing recycling process can achieve high recoveries for all useful metals, including Li (92%), Co (93%), Ni (96%) and Mn (98%).

[0104] Recovery efficiency

[0269] A high recovery rate is essential for an effective recycling strategy [XiaoI 2017]. The recovery efficiency (a) is defined by equation (1):

[0105] [ka]

[0106]

[0270] m(N, flash product) and m(N, reactant) represent the weight of the studied species N in the flash product and reactant, respectively. The amount is determined by ICP-OES and calculated by equation (2).

[0107] [ka]

[0108]

[0271] C(N, products) and C(N, reactants) represent the mass concentrations of M species in the dilute solutions of flash products and reactants, respectively. t (N, products) and m1(N, reactants) represent the masses of the diluted solutions of the flash products and reactants. m2(N, reactants) and m2(N, products) represent the masses of the samples used in the ICP-OES experiments. m3(N, reactants) and m3(N, products) represent the total mass of the sample before the flash reaction and the mass of the sample after magnetic separation, respectively.

[0109]

[0272] The molar ratio (β) is determined by Equation 3.

[0110] [ka]

[0111]

[0273] n (N) and n0 (N) represent the actual amount and theoretical moles of the studied species N in the cathode material, respectively. The actual moles are determined by ICP-OES and calculated by Equation 4.

[0112] [ka]

[0113]

[0274] M(N) represents the molar mass of species N.

[0275] Recovery efficiencies from various flash products (Figures 10A-10D) are quantified using inductively coupled plasma optical emission spectroscopy (ICP-OES). For flash recycling of LCO, the average yields are 92% for Co and 77% for Li after a single flash (Figure 11A). These efficiencies can be improved after re-flashing of the non-ferromagnetic parts, such that after one re-flash, the total recoveries for Co and Li are 98% and 85%, respectively. Compared to traditional pyrometallurgical methods, higher Li recoveries can be achieved without sacrificing the Co yield. [Velazquez 2019; Hu 2021; Xiao II 2017; Wang 2018; Assefi 2020]. These values ​​are also close to the leaching efficiencies of hydrometallurgical methods, as shown in the blue areas of Figure 11B and Table III, but flash recycling does not result in the generation of corrosive aqueous waste. [Zhang 1998;Swain 2007;Pinna 2017;Lee 2002;Chen 2015].

[0114] [Table 3]

[0115]

[0276] The same trends can be found for flashed NMC (fNMC) and actual CW with mixed components obtained from spent LIBs. A single flash of NMC resulted in high average recoveries for all useful metals (Figure 11C), including Li (94%), Co (94%), Ni (98%), and Mn (92%). High average recoveries were also achieved for flashed CW (fCW, Figure 11D), including Li (92%), Co (93%), Ni (96%), and Mn (98%). Radar plots (Figures 11E-11G and 12A-12F) compare metal recoveries of the flash method with typical efficiencies found in pyrometallurgical and hydrometallurgical methods.

[0116] Structure retention factor (R)

[0277] The structural retention factor is defined as the existing 3D layered cathode structure after the recycling method. The structural retention factor is only present in flash recycling. It highlights the retention of the particle morphology and crystalline structure after the flash process and can be quantified by X-ray diffraction (XRD).

[0117]

[0278] The structural retention factor (R) is defined by equation (5).

[0118] [ka]

[0119]

[0279] I(003) and I(104) represent the intensities of the (003) and (104) peaks in the XRD spectrum. I0 and I represent the peak intensities of the reactants and products from different recycling processes. In the XRD results, the (003) peak is characteristic of the layered structure in lithiated metal oxides, and the (104) peak reflects the characteristics of the basic unit of transition metal-oxygen bonds forming layered compounds. The intensity ratio between the (003) and (104) peaks indicates the efficiency of crystallization. Lower values ​​of I(003) / I(104) reflect cation mixing between transition metals and lithium, and generally decomposition of the layered features.

[0120] (1) R = 0 corresponds to the case where the layered structure disappears. (2) 0 < R < 1 corresponds to the case where the layered structure is preserved but the crystallinity deteriorates. (3) R ≥ 1 corresponds to the case where the crystallinity is improved and the layered structure is preserved.

[0121]

[0280] In the case of hydrometallurgy and pyrometallurgy methods, the layered structure of the cathode waste material no longer exists, and R = 0. Conversely, the flash recycling method can preserve the structure, and R = 3.29 / 3.22 = 1.02. This value reflects that the layered structure was preserved without deterioration of the crystallinity during the flash recycling method.

[0122] Hierarchical structure of fine particles in cathode materials

[0281] The efficiency of the flash recycling process in the cathode material was determined by analyzing the subsurface region of the ferromagnetic part and the crystal structure of the bulk by elemental depth analysis and XRD, respectively [Andre 2015]. The distinct elemental ratios and valence states from the surface to the subsurface elucidated the hierarchical structure of the cathode microparticles resulting from the flash recycling process.

[0123]

[0282] In the case of fCW, the atomic ratio of Co increases dramatically from < 1% to about 20% when processed at a depth of 500 nm from the surface, and the binding energy shifts down from 782.2 eV at the surface to 779.3 eV (less than 200 nm, Figures 13A - 13B), while the carbon content decreases in the corresponding region (Figure 13B). The splitting of the O 1s spectrum into O α (at about 532.6 eV) and O β (at about 530.3 eV) indicates the transition from adsorbed oxygen species to lattice oxygen species (Figures 14A - 14E) [Chen 2015].

[0124]

[0283] This, combined with the unchanged binding energy of the Co 2p spectrum below 200 nm, confirmed the presence of intact lithiated metal oxide in this region (Figure 13C). Conversely, the unflashed CW did not show any significant change in binding energy or elemental content below the solid electrolyte boundary formed during the battery cycling process (Figures 15A-15G). This result confirms that there is a layered structure of the cathode particles formed by the flash recycling process. Similar topological structures were found in the flash recycled LCO and NMC (Figures 16A-16F, 17A-17F, 18A-18H, and 19A-19H), which indicated the broad applicability of the flash recycling method to process different cathode materials.

[0125]

[0284] The layered structure of the magnetic part of the flash-recycled CW is further confirmed by the (003) diffraction peak at about 18.9° [Dai 2019], while the non-magnetic part is composed mainly of graphite conductive additives, with some residual metallic signals (Figs. 20A-20B). Similarly, there is an intact layered structure in flashed LCO (fLCO) and fNMC (Figs. 21A-21B and 19A-19B). The emergence of magnetic properties in fCW clarifies one relevant aspect of the flash method. Localized rapid heating and cooling causes pyrolysis that is limited to the surface only, while maintaining the grain integrity. This process affects the CEI, the cathode surface, the carbon coating, and the ability to resynthesize new cathodes.

[0126]

[0285] CEI breaks down into salts that coat the particles. The presence of carbonates is indicated by the CO3 2-This can be confirmed by the stretching modes (Figures 23A-23D, 24A-24D, 25A-25F, and 26A-26F) and the high binding energy in the XPS C 1s spectrum [Li 2019]. The carbon present in the electrode is also rearranged as a thin coating on the surface of the particles at high temperatures, as evidenced by elemental mapping (Figure 13D). The thickness of the carbon is 20-50 nm, identified by focused ion beam milling combined with SEM images (Figures 27A-27E) and elemental depth analysis shown in the XPS results (Figures 14A-14E). As shown in Figures 27D-27E, the elements Co and O are enriched in the cross section where C is absent, while the top surface shows the presence of C and the absence of Co and O. This indicates that there is a carbon coating on the surface of the ferromagnetic fCW particles, and that the thickness is 20-50 nm, inferred from the cross-sectional SEM images and XPS depth analysis. The carbon coating is derived from a flash reaction between the cathode particles and the conductive carbon additive. During the flash reaction, which takes place in 10-30 ms, hot spots are formed only at the interface between the conductive carbon and the insulating cathode material. These hot spots are resolved by the formation of a thin carbon coating (20-50 nm) on the cathode particles and the deposition of Li at the interface without irreversible layered structure collapse. + This leads to the formation of a metal oxide (approximately 200 nm) below the surface after diffusion.

[0127]

[0286] The cathodic surface reactions can be particularly important. Flashing induces the formation of metal oxide films from two sources: rearrangement and decomposition. The flashing process thermally decomposes the particle surface with the release of O2 and delithiation. This surface modification results in the formation of Co at the surface. 2+This leads to the formation of LiCoO2-containing species, e.g., Co3O4 and CoO, which have enhanced magnetic susceptibility compared to lithiated species [Sharifi 2017]. It has been shown that this process can occur at temperatures below 300 °C in aged cathodes [Furushima 2011]. Oxides may also form naturally as part of cycling or may be rearranged by the flash process. As a result of repeated charge / discharge cycles, the surface of the CW particles is divided into regions of crystalline LiCoO2, partially delithiated LiCoO2, and partially delithiated LiCoO2. x It consists of domains of CoO2 and small inclusions of Co3O4 and CoO phases. [Kabir 2017]

[0128]

[0287] During the FJH process, this heterogeneous material undergoes an annealing process during which it is encapsulated with a carbon shell that prevents significant mass loss. Upon structural relaxation, Co3O4 and CoO undergo outward segregation (Figure 13E) and form a shell on the restored crystalline LiCoO2. Part of this surface metal oxide can be identified in high-resolution transmission electron microscopy (HR-TEM) images (Figures 28A-28B and 29A-29H).

[0129]

[0288] First-principles calculations show that the energy direction of such segregation, ΔE, is (Figure 30). First-principles calculations show that the partially delithiated LiCoO2 via phase segregation of Co3O4 and the release of O2 gas. x This allowed the demonstration of possible pathways for the annealing process of CoO2 [Furushimna 2011]:

[0130] [ka]

[0131]

[0289] Reaction energy ΔE = E for various values ​​of x LiCoO2 +E Co3O4 +E O2 -E LixCoO2is plotted in Figure 30, showing the energy directing to phase segregation. Interestingly, note that the energy directing to segregation is minimal at low to moderate delithiation levels.

[0132]

[0290] A relatively lower ΔE is observed for the new cathode compared to the old cathode, indicating that annealing during flash recycling is more effective for the aged cathode since delithiation is more pronounced. This mechanism is consistent with the increase in the structural retention factor, as can be observed in Figures 11E, 12A, and 12D. The flash cathode material retains about 93% of the original grain size distribution of the cathode material (Figures 23A-23D, 24A-24D, 25A-25F, and 26A-26F). The surface decomposition is further evidenced by X-ray diffraction (XRD). A downshift of the diffraction peak (003) (widening of the interlayer spacing) has been observed in the ferromagnetic part of the fCW (Figures 20A-20B), which is consistent with a partial delithiation process (Figures 31A-31C).

[0133]

[0291] The magnetic properties of the Co3O4 / CoO film were simulated (Figure 13E), presenting a magnetic moment of about 70 emu / g of the bulk phase (about one-third that of Fe at 219 emu / g). The magnetic signature of the oxide shell is somewhat reduced by intrinsic disorder and size effects, characteristics consistent with those of thin Co3O4 films [Apatiga 2006; Moro 2013; Zhang 2015]. The formation of this layer is useful (and can be exploited) for magnetic separation. The stepwise nature of the annealing is consistent with the ability to improve recycling yields via repeated FJH of non-magnetic materials observed in experiments.

[0134] Re-synthesized cathode material

[0292] The cathode material may be resynthesized from the ferromagnetic flash product, in which context the cathode material is referred to as "re-synthesized cathode" (R-CW). For example, about 1 g of the flash product was mixed with 10 mL of 4 mol / L LiOH aqueous solution, and then the mixture was poured into a hot water container. The hot water container was made of polytetrafluoroethylene and had a volume of 40 mL. The container was then sealed in a well-fitted stainless steel autoclave and placed in an oven at 180°C for 12 hours. The solid powder was then dried using vacuum filtration. The solid was then calcined in air at 400°C for 3 hours before being used to prepare a battery slurry.

[0135]

[0293] In terms of synthesizing new cathodes, the flash process results in more efficient use of Li. Compared with the solid-state reaction to prepare resynthesized cathodes, the hydrothermal method disclosed and described herein can avoid the direct use of solid Li sources, which are difficult to remove after the resynthesis process and act as impurities to affect the electrochemical performance of the cathode material. As reported in the literature [Zhao 2020; Zhang 2014], the chemical potential of the layered flash product Li 0.84 Chemical lithiation of CoO2 (stoichiometric ratios are calculated from ICP-OES) can be driven to form the final resynthesized cathode material. Since there is no fundamental structural change, the optimization conditions can be milder compared to the synthesis conditions starting from rock-type metal oxides such as Co3O4. LiOH is used as the Li source because it has excellent water solubility to form a concentrated solution. Other Li sources such as Li2CO3 have also been reported as Li sources for the synthesis of LCO [Zhao 2020], and these can also be considered in industrialized processes. The purpose of the final calcination step is to increase the crystallinity and improve the electrochemical performance of the resynthesized cathode material, and the reason for choosing 400 °C in the embodiment can be explained by the results, because at temperatures higher than 450 °C, carbothermal reduction begins [Wang 2018].

[0136]

[0294] The formation of lithium carbonate on the surface of the ferromagnetic flushed particles minimizes the need for replenishment of Li-ion precursors to reconstitute the stoichiometry of the newly recycled cathode, see FIG.

[0137]

[0295] To calculate the Li source consumed in the resynthesis process, the solvent after the hydrothermal reaction is collected. A TGA can be performed (Figure 32) to calculate the remaining Li source, e.g. impurities in the water of crystallization. There is one mass loss stage by TGA in the LiOH·H2O reactant at about 120 °C, which is related to the loss of water of crystallization in the reactant. For the recovered Li material, there are three stages. (1) At about 100 °C, the loss (about 5.6%) is related to the loss of water of crystallization. (2) At about 600 °C, the loss (about 31.0%) is related to the decomposition of LiOH. (3) At about 860 °C, the loss (about 8.9%) is related to the decomposition of Li2CO3, and the remaining powder is Li2O. [Beyer 2013]. The mass of the recovered powder is 1.0259 g. Therefore, the mass of Li in the recovered powder is 0.2686 g. Since the mass of Li in the reactant powder is 0.2804 g and about 1.0 g of flash powder is used, the percentage of Li consumed is 18.4%.

[0138]

[0296] Only 10%-20% of the new Li ions are needed to fully lithiate and reconstruct the cathode material, since 80%-90% are already present in the ferromagnetic flash product as shown by ICP-OES (Figures 33A-33E, in which the corresponding cobalt complex is shown with its required Gibbs free energy). New cathode material may be resynthesized from the ferromagnetic fCW by a simple hydrothermal reaction followed by calcination at 400 °C in air.

[0139]

[0297] For certain embodiments, the optimized calcination temperature is 400° C., with a higher temperature of about 500° C. expected for carbothermal reduction to occur. Therefore, the following characterization is for R-CW-400, which for simplicity will be referred to as R-CW. The possible reactions of LCO and the corresponding Gibbs free energy relationships can be calculated as follows:

[0140] [ka]

[0141]

[0298] We plotted the Ellingham diagram of the above reaction, which confirms the thermodynamic relationship [Wang 2018]. The carbothermal reduction of carbon and LCO is thermodynamically favorable under inert atmosphere or in air. Therefore, high-temperature calcination may cause the reduction of Co species, which is not good for cathode material resynthesis. Similarly, direct high-temperature processing in pyrometallurgical methods may only obtain Co3O4 metal mass resulting from the above carbothermal reaction. The thermogravimetric curve also demonstrates that LCO itself is stable in air when the temperature exceeds 1000°C, but the ferromagnetic part of fLCO, which is coated with carbon, shows a weight loss of more than 10 wt% when the temperature increases from 600°C to 800°C. This can also be explained by the above carbothermal reaction. When holding the temperature at 500°C for 30 minutes, an obvious mass loss can still be observed, as shown in Figure 33E. This is consistent with the XRD in Figure 33B.

[0142]

[0299] In order to coat the cathode material with carbon, a low calcination temperature should be used in the last step of the resynthesis process. However, the resynthesized cathode obtained by pyrometallurgical or hydrometallurgical methods requires a high calcination temperature (higher than 750 °C) to build an ordered layer structure of the cathode [Zhao 2020; Moro 2013; Nie 2015]. This feature makes it more difficult to directly achieve surface carbon coating in such classical resynthesis processes, and it is expected that more complicated post-treatment will be required if carbon coating is required after pyrometallurgical or hydrometallurgical recycling protocols.

[0143]

[0300] The resynthesized cathode material (R-CW) loses ferromagnetism and shows a 3D layered structure with high crystallinity. For Figs. 34A-34I, 35A-35E, 36A-36C, and 37A-37J. For Figs. 36A-36C, the amorphous carbon coating can prevent direct exposure of the NMC cathode particles in the corrosive carbonate electrolyte and reduce the parasitic reaction between the NMC and the electrolyte under high voltage conditions. It was also confirmed that the amorphous carbon coating is Li-ion permeable, unlike the well-graphitized carbon coating. Therefore, the flash Joule heating method can be used to coat the cathode material. For Figs. 37A-37J, the presence of a thin carbon coating can be seen on the surface of the R-CW particles.

[0144]

[0301] The high-resolution TEM image in FIG. 13F and the corresponding fast Fourier transform (FFT) pattern show the presence of a layered structure on the surface of the cathode particles.

[0302] Atomic resolution high angle annular dark field scanning transmission electron microscopy (HAADF-STEM) imaging (Figures 13G and 38A-38D) shows the presence of a trigonal lattice along with the space group (compared to fLCO, which has a spinel structure as shown in Figures 29A-29H, Figures 38A-38D show the presence of a recovered layered structure in the resynthesized cathode material).

[0145]

[0303] These results reflect the recovered layered structure in the resynthesized cathode material. The amorphous carbon coating on the R-CW particles is also retained after the resynthesis process, as shown by SEM (Figures 34A-34I), HR-TEM (Figures 36A-36C), STEM and corresponding elemental mapping (Figures 13H and 37A-37J). Similarly, a layered structure was seen in R-LCO, and energy mapping indicated the presence of a carbon coating (Figures 34A-34I).

[0146] Atomistic simulation

[0304] The partially graphitized carbon crust may also be important in cell performance, since its Li-ion permeability is a factor in electrochemical processes. The AIREBO interatomic potential was used to simulate high-temperature annealing during flash recycling for large amorphous carbon structures containing more than 30,000 atoms. The initial configurations included small graphitic domains with arbitrary shapes, ranging in size from 8 Å to 22 Å and up to three layers thick, randomly positioned within the periodic cell with misalignments of up to 50 degrees. The remaining 65% of the atoms were provided as individual carbon atoms randomly positioned within the unit cell. The resulting configurations were pre-annealed and slowly heated to the target temperature. For comparison, Figures 39A-39E show the results of annealing at 700K, 1000K, 1500K, 2000K and 2500K.

[0147]

[0305] Simulation at high temperature (2500K) is 0.9g / cm 3 The figure shows a completely amorphous carbon with a density of 1.2 kcal / cm2 (Figure 13I). Using first-principles calculations, we found that the Li + To confirm the effect of annealing on the permeability, Li +The diffusion of ions was compared across various features of the carbon structure. A particular role is played by the elimination of non-passivated graphitic edges during annealing. As demonstrated in Figures 40A-40D, the diffusion barrier on these structural elements can reach 1.5 eV, compared to a barrier of 0.34 eV for a perfect graphitic surface. Furthermore, non-passivated edges provide potential energy traps that are expected to capture Li-ions with a negative impact on the battery characteristics.

[0148]

[0306] In the Li2+ surface, diffusion into the reconstructed divacancy is characterized by a barrier of 0.5 eV, similar to that of the graphitic surface. In addition, larger octagonal defects allow transmission through the surface, but a larger barrier of 1.6 eV must be overcome. Furthermore, the edges of well-reconstructed graphite form spherical shapes [Zhang 2012] and act as a continuation of the smooth surface with a diffusion barrier of 0.4 eV. + Does not block diffusion.

[0149]

[0307] First-principles calculations show significant differences in the effect of various structural elements within the amorphous carbon crust on Li-ion diffusion; Figures 39A-39E and 40A-40D. Annealing improves the Li-ion permeability of the crust, as observed, by eliminating non-passivated graphitic edge and point defects (see Figure 13I).

[0150] Flash Recycling Process Life Cycle

[0308] The electrochemical cycling performance of the flash-recycled R-CW was studied in a half-cell with an initial configuration of R-CW / Li. The R-CW shows obvious decay in the first 10 cycles, but a slower capacity fade is observed from 25 to 200 cycles compared to fresh LCO and fresh NMC cathodes without the flash-produced carbon coating assembled under the same laboratory conditions (Figures 13J and 35A-35E). The R-CW is much more stable than the pristine CW.

[0151]

[0309] The improved cycling performance of the R-CW may be due to the carbon coating acting as an artificial CEI to avoid direct exposure of the cathode particles while having high oxidative stability in the electrolyte. This reduces irreversible active material loss during the electrochemical cycling process. Further optimization to minimize the decay in the first 10 cycles is expected to increase efficiency, but even at this preliminary level of study, the R-CW outperforms new cathode materials in similarly constructed systems. The ability to rapidly generate such a stabilized and Li-ion permeable carbon coating without solvents or pastes may be particularly important for the newer, higher capacity but relatively less stable NMC cathodes, so this flash approach can be used not only for recycled materials but also for new cathodes.

[0152]

[0310] Using the Everbatt 2020 software package developed by Argonne National Laboratory to determine closed-loop life cycle analysis of LIBs [Everbatt 2020], the flash method was compared to different types of recycling processes and their efficiencies. Figures 41A-41F and 42A-42D.

[0153]

[0311] A scheme of closed-loop life cycle analysis of LIBs illustrates the various phases during the recycling process. Figure 42A. Direct recycling processes, such as repair and repurposing, are easily operated but generally result in cycle-reduced and down-regulated cathode materials. In contrast, current recycling processes, such as pyrometallurgical or hydrometallurgical methods, involve complex steps to recover useful metals in elemental and compound forms. However, these methods irreversibly destroy the structure of high-performance cathodes and require extra resynthesis steps before they can be returned to service life. The FJH method achieves high recovery rates without losing the layered structure of the cathodes and reduces the operation period.

[0154]

[0312] Flash recycling does not destroy the layered structure of the cathode, facilitating its reuse in fully performing batteries. FIG. 13J. Using the LCO type cathode as a model, flash recycling reduces recycling costs by about 45%, recycling energy by about 70%, and GHG emissions by about 70%, while increasing the profitability of recycling by about $25 / kg cathode and about $18 / kg cathode, respectively, compared to pyrometallurgical or hydrometallurgical methods. See FIG. 41B-41E. With growing interest in cathode materials with lower Co content, such as NMC622, NMC811, and NCA, as well as non-Co based systems, such as LiFePO4 and LiNiO2, flash recycling using these other ferromagnetic metals may bring more efficient recycling with increased profit margins within reach. FIG. 41F.

[0155]

[0313] It should be noted that there is a difference in revenue between pyrometallurgy and others due to combustion for energy rather than sale. Utilization of this feedstock in different recycling methods is shown in Table IV.

[0156] [Table 4]

[0157]

[0314] Flash recycling of LIBs is therefore an environmentally cleaner way to regenerate metals in secondary batteries. The method preserves the 3D layered structure of the cathode and provides efficient reuse of elemental inventory. The rapid process also results in a convenient carbon coating on the recycled cathode particles that stabilizes the overall structure of the cathode while allowing Li-ion transport, thereby providing recycled batteries with superior performance over new batteries. The FJH process can be industrially scaled to multi-ton scale per facility [Universal Matter 2021], thus enabling ease of manufacturing while minimizing reliance on newly mined metal ores for LIB production.

[0158] Flash recycling process for anode materials.

[0315] High-temperature calcination (1200-3000 K) is still the predominant process for regenerating graphite, but it is time- and energy-consuming, accounting for more than 50% of the recycling cost. The use of strong corrosive acids such as HCl and H2SO4 also raises serious concerns about secondary waste. Besides, calcination leads to the formation of toxic and corrosive exhaust gases, e.g. HF, making these methods less promising for the treatment of original anode waste (AW) directly recovered from lithium-ion batteries (LIB).

[0159]

[0316] A solvent- and water-free flash recycling method is discovered to reactivate AW collected directly from spent LIBs. The method is completed within seconds and preserves the morphology of graphite particles. The estimated energy cost is only about $67 to flash recycle one ton of original AW. After the flash recycling process, the mosaic-like SEI can be decomposed and graphene shells are formed on the surface of the graphite particulates. The formation of graphitic layers from the SEI embedded with inorganic salts, e.g., LiF, Li2CO3, and Co3O4, can be observed. These inorganic salts can be easily recollected from the graphite by post-treatment with 0.1 M HCl solution. The flash anode product shows a recovered specific capacity (358.9 mAh / g at 0.2 C) compared to the original AW and commercial graphite materials. Life cycle analysis (LCA) and comparison with current calcination processes show that the flash recycling process can significantly reduce total energy and water consumption, as well as greenhouse gas (GHG) emissions, indicating the environmental and economic prospects of the flash recycling process.

[0160]

[0317] In an embodiment, an ultra-fast solvent-free flash joule heating (FJH) method regenerates battery graphite anodes in bulk dry powder form from battery anode waste. Characterization of the flash recycling product shows intact 3D layered graphite core structure coated with graphene shells derived from the solid electrolyte interphase (SEI). Valuable metals, lithium, cobalt, nickel, and manganese, can be easily recovered from the flash anode product by post-treatment with dilute acid. The flash anode material shows restored electrochemical performance compared to anode waste and new commercial graphite. Life cycle analysis compared to current calcination methods highlights that flash recycling can turn anode recycling into an economically advantageous process while significantly reducing total energy and greenhouse gas emissions.

[0161]

[0318] The FJH system is similar to the one described above [Luong 2020; see also Chen 2021]. Figures 43A-43B show the circuit diagram of the FTH setup and an illustration of the FJH reaction box. In an exemplary embodiment, Ar gas (~1 atm) was used as an inert atmosphere to avoid oxidation of the sample during the FJH reaction. The reactants were graphite anode waste collected from the anode side in used Li-ion batteries. The reactant powders were ground and mixed uniformly by a mortar and pestle, and then loaded into reaction tubes with an inner diameter of 8 or 16 mm. The reaction tubes may be quartz or ceramic tubes, or concrete, or other non-conductive materials. The masses loaded into the 8 mm and 16 mm tubes were 200 mg and 1 g, respectively. A graphite rod was used as the electrode in this reaction. The compression force was controlled by a small vice connected to a rotary knob, as shown in Figure 43B, and the sample resistance was adjusted to about 2 Ω. An Arduino controller with a programmable millisecond-level delay time was used to control the discharge time, and the electricity was provided by a capacitor bank with a total capacitance of 60-222 mF. The capacitor bank was charged by a DC power supply capable of reaching 400 V. For the 8 mm tube reaction, the FJH reaction was carried out with a voltage of 120 V and an optimized duration of 1000 ms (further details are given in Table V). After the FJH reaction, the device was allowed to cool and evacuated for 3 min. In this context, the product is called flash anode waste (fAW).

[0162] [Table 5]

[0163]

[0319] In a typical flash recycling process, AW collected from spent lithium-ion batteries (LIBs) is used directly as a reactant without further processing. The AW, in powder form, is slightly compressed inside a quartz tube between two graphite electrodes (Figures 43A-43B). A capacitor bank in the circuit is used to provide electrical heat energy to the AW reactant for about 1000 ms (Figures 44A-44B). During a typical flash recycling process with a voltage of 120 V and a resistance of about 1.3 Ω, the current passing through the sample reaches about 350 A with a discharge time of about 1000 ms (Figure 44C). The total amount of electrical energy is 1210 J / g, the majority of which (>80%) is targeted to heating and decomposing the SEI (continuous phase), while the graphite particulates (dispersed phase) receive only <20% of the electrical energy according to the Joule heating distribution law (Figure 44C). This effect of Joule heating of the continuous phase reflects the selective reaction of the resistive layer (continuous phase) at the interface, in our case the graphitization of the SEI.

[0164]

[0320] In the conventional calcination process (Figures 45A-45B), the entire system, including the environment and anode waste, is subjected to high temperatures (>1300 K) for several hours under inert atmosphere protection, which demands high energy consumption, generates more GHGs, and also generates secondary waste [Yu 2021]. The flash recycling process achieves instantaneous localized heating of the AW with the desired selectivity, and the environment facilitates the subsequent rapid heat transfer from the reactants to avoid thermal expansion and defect formation. The temperature is measured by a high-temperature infrared thermometer, with the maximum temperature being about 2850 K. During the flash process, the ultrafast heating rate is about 1.6 × 10 5 K / s, and the cooling rate is about 9.2×10 3 K / s (Figures 45A to 45B).

[0165]

[0321] To confirm the decomposition of the SEI structure and evaluate the removal of "dead mass" in the flash recycling process, thermogravimetric analysis (TGA) is used due to the distinct thermal stabilities of the SEI, binder, and other components, such as graphite or inorganic salts (Figures 46A-46D) [Beyer 2013; Advincula 2021].

[0166]

[0322] For the pristine AW, there is a mass loss of about 16.3% at 773 K (Figure 47), but after the flash reaction, the mass loss is dramatically reduced. After flashing at 120 V for two cycles, the mass loss becomes negligible (about 1.2%), which may be caused by the decomposition of lithium salts such as LiOH, as shown by the differential scanning calorimetry (DSC) results (Figure 46B) [Beyer 2013]. Similar results are also observed for the calcined AW (cAW), which is prepared by calcination at 1323 K for 1 h under argon protection, with minimal mass loss at 773 K. A significant reduction in mass loss can also be found after scaling up the present system to the gram level, and the visual images of various anode materials can be seen in Figures 48A-48F. Hence, the flash process can effectively decompose the SEI and remove the "dead mass" accumulated in the pristine AW. Notably, at 1273 K, the remaining solids comprise approximately 12.1% of the flash product, compared to <4.0% for cAW (Figure 49). The difference in remaining weights indicates that the flash recycling method preserves inorganic salts and facilitates subsequent metal collection.

[0167]

[0323] To investigate the changes after the flash process, the crystal structure of the bulk and the surface / subsurface regions of the flashed products are analyzed by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), respectively. In Figures 50 and 51A-51B, the crystal structures of flashed AW (fAW) and cAW are compared with the pristine AW. High-temperature calcination removes most of the organic and inorganic impurities remaining in the pristine AW, and only the diffraction peaks of graphite can be identified. [Advincula 2021]. The flash recycling process can decompose the SEI structure with the conversion to other species such as LiF that are not present in the pristine AW. The (002) diffraction peaks of both cAW and fAW are centered at about 26.5°, which indicates an interlayer distance of about 3.36 Å, consistent with the layered structure of graphite. The presence of LiF and Li2CO3, as well as a layered structure of graphite with a similar interlayer distance (~3.36 Å), is also observed in fAW synthesized from large batches (Figures 52A-52C).

[0168]

[0324] Compared with AW, which is rich in F (23.8%), O (14.4%) and P (1.9%) on the surface, fAW shows a relatively high content of C (89.6%) and a reduction in other nonmetallic elements, such as F (5.7%), O (2.9%) and P (<0.1%) (Figure 53 and Table V). cAW also has a high content of C (92.8%) and reduced contents of other elements, such as F (1.1%) and O (6.1%) on the surface (Figure 54). Depth analysis of the original AW shows obvious ratio changes of various elements, such as Li and F, from 0 to 200 nm and becomes relatively constant below 200 nm (Figures 55A-55F), reflecting the elemental composition and SEI at the top of the graphite microparticles.

[0169]

[0325] The flash recycling process can decompose the SEI structure and modify the subsurface region at least 500 nm deep, while reducing the content of nonmetals such as O, F and P at the surface (Figures 55A-55F). The reduction of nonmetal content observed in fAW is comparable to the results in cAW prepared by high-temperature calcination. The removal of the original organic SEI and electrolyte residues on the original AW can be further confirmed by UV-vis spectra. After dispersing the original AW in deionized water, the supernatant exhibits a yellowish color and has a broad peak centered at about 220 nm, which can be attributed to the oxidized carbonate electrolyte and organic SEI. [Bouteau 2019]. In comparison, fAW dispersed in water at the same concentration (about 5 mg / mL) results in a clear solution. A small transition peak located at about 230 nm is observed from the fAW, which is attributed to the presence of LiF salt (Figure 56). [Baldacchini 2004].

[0170]

[0326] As shown by scanning electron microscopy (SEM) and the corresponding particle size distributions (Figures 57A-57L), the bulk structure of the graphite particulates is preserved and the average size (about 15 μm) is similar after the flash recycling process.

[0171]

[0327] To identify the changes in the surface structure, high-resolution transmission electron microscopy (HR-TEM) was performed, as shown in Figures 58A-58D and 59A-59D. In the case of AW (Figures 58A-58D), there is an amorphous layer on the outside of the graphite microparticles, with the average thickness of the layer reaching about 145 nm. The graphite lattice fringes can be identified below this layer. Within the amorphous layer, there are several small embedded Li2CO3 crystals, which is consistent with the mosaic model of the SEI structure.

[0172]

[0328] After the flash reaction (Figures 59A-59D), the SEI layer is pyrolyzed, the carbon portion is graphitized, and the average thickness is reduced to about 65 nm. A graphene shell can be seen in the outermost region with embedded nanoparticles such as Co3O4 and LiF formed from elements in the SEI layer of the original AW. This can be inferred by the scanning TEM (STEM) and corresponding element distribution results (Figures 60-61).

[0173] Metal recovery

[0329] These metal nanoparticles and salts appear to be trapped by the modified graphene layers, but they can be removed by rinsing the material with dilute acid. Therefore, useful metals, such as Co and Li, can be recovered from the fAW by simple acid post-treatment. The presence of Co in the SEI on the anode side is not unexpected. Cobalt dissolution from lithiated metal oxide cathodes has been observed in batteries at end-of-life [Li 2020]. Since the SEI traps electrolyte, it is expected that it will also accommodate a concentration of dissolved Co ions, which are converted to metal oxide nanoparticles in flash recycling.

[0174]

[0330] To recover useful metal ions from the flash product, HCl solutions with different concentrations are used for comparison. Two factors, recovery efficiency (α) and excess yield Y / Y0, are defined to evaluate the recovery results. α is the recovery rate of one species (metal from AW, fAW, or cAW) relative to the recovery rate performed by concentrated acid, and Y / Y0 is the yield obtained from various treated anode materials (fAW or cAW) relative to the yield obtained from the original AW using the same recovery procedure.

[0175]

[0331] Compared with concentrated hydrochloric acid (10-11 M) currently used in the battery recycling industry, dilute hydrochloric acid (0.01-1 M) can also effectively recollect metal ions from the flash product, with the average recovery efficiency reaching about 97.5% by using 0.1 M HCl (Figure 62A). By using 0.1 M HCl, the total amount of metal ions recovered from the fAW was also higher than that recovered from the original AW, with an average excess yield of 1.12, indicating that 12% more metal ions can be collected from the flash product. This result is supported by STEM images and elemental mapping showing the formation of metal oxide nanoparticles and polar salts such as Co3O4 and LiF after the flash reaction.

[0176]

[0332] Compared with the organic salts formed in the SEI, these inorganic metal oxides and polar salts can be completely dissolved in a more dilute acid solution. Therefore, the average recovery efficiency for each metal ion, e.g., Li (99.4%) and Co (80.1%), is high even when treated with 0.1 M HCl solution (Figure 62B). The average excess yields of Li and Co were 1.10 and 1.19, reflecting that 10% more Li and 19% more Co could be collected from the flash product than from the original AW.

[0177]

[0333] In comparison, direct high-temperature calcination causes the evaporation of these metal sources, which may be concentrated downstream and corrosive to devices such as metal chambers and glass pipelines. Therefore, only <15% of the total metal ions can be collected in the different HCl solutions (Figure 62C). The TGA results show that for pristine AW and fAW, after heating to 1273 K under air, the weight percentages were 10-15 wt%, and the remaining solids are the main source for the different metal ions (Figure 62D).

[0178]

[0334] Figure 62E shows the absolute amounts of the different metal ions in the material and compares the extent of recovery and excess yields obtained from different recycling conditions and materials. The total concentrations of Li, Co and Ni reach 15314, 898 and 124 ppm in the fAW, which are higher than in natural sources such as ores and brines (100-1000 ppm for Li) or seawater (<0.21 ppm for Li). Besides, these metal species can be easily recollected by dilute acid solutions, and there is no evidence of Na in the fAW. + (approximately 13,000 ppm in seawater), Ca 2+ , Mg 2+ and K. + There are almost no interfering ions such as ZnO, Fe, and ZnO. After rinsing the fAW with 0.1 M HCl solution and then heating to 1273 K under air, almost no mass remains and only graphite diffraction peaks can be identified, indicating effective recovery of various useful metal ions from the fAW compared to the pristine AW (Figs. 63A-63B). HR-TEM and corresponding Fast Fourier Transform (FFT) results of the rinsed fAW sample (fAW-W) show the disappearance of these nanoparticles and a series of six-fold diffraction patterns along the

[0002] zone axis, thereby confirming the recollection of various useful metal ions and the preservation of well-graphitized anode particles (Figs. 64A-64D). The use of dilute HCl solution greatly reduces possible equipment erosion and mitigates possible hazards to workers and the environment, so the flush recycling method may be applied to regenerate the anode and recover the metal source.

[0179] Effectiveness

[0335] To evaluate the effectiveness of the flash recycling method, the electrochemical properties of various anode materials, such as bulk resistivity, rate capability and electrochemical stability, were tested. The polarization occurring during the charge and discharge process caused by the accumulation of SEI and surface amorphization is one of the main reasons for anode failure. As listed in Table VI, the significant decrease in bulk resistivity (about 63%) from AW to fAW indicates the decomposition of the resistive SEI, and the resistance of fAW is still larger than the intrinsic graphitic material due to the surface coating of the fluorinated layer obtained by the flash process. This fluorinated layer can act as an artificial SEI layer to improve the reversibility in the first cycle associated with the formation of a new SEI, which is responsible for the electrochemical stability in the subsequent charge and discharge processes.

[0180] [Table 6]

[0181]

[0336] The skeletal density of the anode material is approximately 2.2 g / cm 3 As shown in Figure 65, the coulombic efficiencies (CE) of fAW, cAW and graphite in the first cycle are 84.4%, 74.3% and 80.3%, respectively. The areal capacity of the tested anodes is about 3.0 mAh / cm 2 The results indicate that fAW exhibits less irreversible loss of electrochemically active Li species compared to cAW and commercial graphite.

[0182]

[0337] The reduction of solution components, including solvent and salt anions, and the simultaneous growth of the SEI, are responsible for the increase in the potential for 0.5–1.5 V(Li / Li +fAW has the smallest irreversible capacity loss (~20 mAh / g) compared to AW (~46 mAh / g) and commercial graphite (~37 mAh / g) due to the high thermal conductivity (vs. 0.1 V). cAW has the largest irreversible capacity loss (~55 mAh / g), which is related to the CE in the first cycle. The favorable SEI formation for fAW reduces the polarization with cycling and leads to a lower overpotential, especially at higher rates (>0.5 C), compared to graphite, pristine AW, and cAW (Figures 66A-66C).

[0183]

[0338] The average specific capacity of fAW is 341.5, 331.9, 233.1 and 154.1 mAh / g at rates of 0.05C, 0.1C, 0.4C and 0.8C, respectively (Figure 67). This result shows enhanced rate performance compared to pristine AW and is comparable to new graphite or cAW due to the removal of resistive SEI by the flash method. When the rate is returned to 0.2C, fAW has a capacity of 358.9 mAh / g.

[0184] Economic and environmental impacts

[0339] The economic and environmental impacts for preparing synthetic graphite, cAW and fAW are compared using GREET 2020 and Everbatt 2020 developed by Argonne National Laboratory. Flowcharts are shown in Figures 68A-68C. SEI can be effectively decomposed within seconds in the flash recycling method by providing local and instantaneous heating to the original AW. There is no need to carbonize or graphitize carbonaceous materials or heat the environment for hours by high-temperature calcination methods, as shown in the preparation of synthetic graphite. Therefore, the flash recycling method reduces recycling costs by about 48%, GHG emissions by about 39%, water by about 98%, and energy by about 48% (Figures 69A-69E).

[0185]

[0340] Since the average price of natural graphite material (battery grade) is about 10 USD / kg [Advincula 2021], the profits on synthetic graphite are negative (-1.75 USD / kg). Therefore, in the modern market, the price of synthetic graphite is higher (about 20 USD / kg) and less competitive. In comparison, the high-temperature calcination method shows a slight positive profit (0.70 USD / kg) and the flash recycling method has the largest positive profit (3.90 USD / kg), which also reflects the potential of the method of the present invention to increase the profit margins from battery recycling.

[0186] use

[0341] Spent graphite anodes can be regenerated by the ultra-high rate and solvent-free flash recycling method disclosed and taught herein.

[0187]

[0342] The resulting flash anode material exhibits an intact 3D layered graphite core structure coated with layers derived from the solid electrolyte interphase (SEI). Valuable metals, lithium, cobalt, nickel, and manganese, can be easily recovered from the flash anode product by post-treatment with dilute acid. The flash anode material exhibits restored electrochemical performance compared to anode waste and new commercial graphite.

[0188]

[0343] A life cycle analysis for current calcination processes highlights that the flash recycling method can be an economically advantageous process while significantly reducing total energy and greenhouse gas emissions.

[0189]

[0344] The formation of coating structures around graphite microparticles demonstrates the feasibility of preparing core-shell or other hierarchical topological structures within seconds by a solvent-free flash method.

[0190]

[0345] In embodiments, the electrolyte may be removed from the anode material, as well as the separator and current collector, hi other embodiments, one or more of the electrolyte, separator, and current collector may be retained with the anode material in the mixture or may be flushed.

[0191] Destruction of the 3D morphology of the cathode

[0346] In some embodiments discussed and described above, the 3D structure of the cathode can be maintained during flash joule heating.However, in some circumstances, no care is taken to preserve the 3D structure of the cathode, for example because the former 3D structure is no longer compatible with newer battery technology.This may be the case, especially since battery designs tend to be upgraded every 2-3 years.In such a situation (where there is no need to preserve the 3D morphology), the only requirement would be to simply obtain the metals Li, Co, as well as Mn, Ni, and Cu, as well as other metals if applicable.

[0192]

[0347] By using pulses of flash Joule heating at higher currents than previously used and described, which would be expected to readily form dissolved metal oxides, it has been discovered that they decompose the 3D cathode morphology. The reuse of useful metals, such as Li, Co, Mn, and Ni, reduces the need for mining from ores and protects the environment. Furthermore, the acid concentrations are much lower than those required by typical hydrometallurgical recycling, and the energy requirements are much less than those required by pyrometallurgical recycling. Furthermore, such higher current FJH methods can obtain lithium salts, unlike those provided by pyrometallurgical methods (described above). Previously, 120V and 30A were utilized for 150ms to 300ms, which used 10wt% conductive carbon additive, when preserving the 3D structure of the cathode. Using the same flash vessel size to destroy the 3D cathode structure, dissolving the metal more readily in the flash vessel as essentially metal oxide and metal(0) was accomplished by increasing the conditions to 120V and 90A to 100A for 500ms while using 33.3wt% conductive carbon additive. Using the same vessel size, volatilizing the metal out of the flash container into a trap can be accomplished by utilizing 120V at approximately 200A to 300A for 500ms to 1s using 33.3wt% carbon additive.

[0193]

[0348] Such high current FJH processes can decompose the cathode material into simple metal oxides that are easily dissolved in dilute acids, such as 0.1 M HCl, and even 0.01 M HCl, down to metal(0). The acids are much less corrosive than the reagents used in current hydrometallurgical processes, such as 12 M HCl and peroxides, and NaOH rinses.

[0194]

[0349] For comparison purposes, FJH was carried out under conditions for preserving the 3D structure (A) and for destroying the 3D structure (B). In the former case (flush conditions for preserving the 3D structure), the conditions were 10 wt% conductive carbon addition, 120 V, 30 Amp, 300 ms flush time for LCO and 150 ms for NMC, and magnetic extraction of the desired contents. In the latter case (flush conditions for destroying the 3D structure), the conditions were 33 wt% conductive carbon addition, 120 V, 100 Amp, 500 ms flush time for both LCO and NMC, and no magnetic extraction was performed, instead rinsing with dilute acid to obtain the desired metal oxides.

[0195]

[0350] The FJH method provided rapid electrical energy within 500 ms, thereby avoiding weight loss of metals with low boiling points such as Li. The metal contents in the flash joule heated reactor remained in the reactor if the graphite electrode spacers were a snug fit. As can be seen in Figure 70, loss of metal due to sublimation was not an issue.

[0196]

[0351] The total amounts of Li and Co from LCO and flashed LCO were measured by leaching with concentrated hydrochloric acid solution. As shown in Figure 71, the recovery rates of Li and Co were about 100% after flashing, indicating no obvious metal loss due to the FJH treatment.

[0197]

[0352] Different concentrations of HCl were used to leach the metal salts. The recovery efficiencies are compared in Figures 72A-72B. As shown in Figure 72A, in the case of Li, by varying the concentration, Li can be effectively recovered from LCO and flash LCO with >90% efficiency (curves 7201-7202, respectively), with slightly higher efficiency being observed from flash LCO. As shown in Figure 72B, in the case of Co, as the acid concentration decreases, the recovery efficiency decreases in LCO (curves 7203-7204, respectively, for LCO and flash LCO). However, in the case of flash LCO, the efficiency of Co does not decrease.

[0198]

[0353] The distribution of metals after FJH was also analyzed separately from the powdered FJH product in the chamber, the quartz tube cell, and the graphite electrode, see Figure 73. Approximately 30% of the metal ions were attached to the quartz tube and graphite, and the remaining 70% was in the powdered product.

[0199]

[0354] The total amounts of Li, Co, Ni and Mn from NMC and flashed NMC were also measured by leaching with concentrated hydrochloric acid solution. After flashing, the recovery rates of Li, Co, Ni and Mn could be about 100%, as shown in Figure 74, indicating that there is no obvious metal loss from the FJH process. It should be noted that the quartz tube is used here only as a convenient transparent container at the research scale. When scaled up, quartz tubes would typically not be used due to their cost and fragility. Other reactor cells such as ceramic, concrete and high temperature concrete would be used. Teflon and polyphenylene sulfide tubes, which are high temperature stable plastics, could also be used because the current does not pass through these insulations and therefore there is little temperature increase in them.

[0200]

[0355] In Figures 75A-75D, curves 7501-7504 show the recovery of Li, Co, Ni and Mn from NMC in HCl solutions at different concentrations, respectively, and curves 7505-7508 show the recovery of Li, Co, Ni and Mn from flashed NMC in HCl solutions at different concentrations, respectively. These curves reveal that 0.1 M HCl was sufficient to remove metal salts from the flashed cathode.

[0201]

[0356] Although embodiments of the present invention have been shown and described, modifications thereof can be made by those skilled in the art without departing from the essence and teachings of the present invention. The embodiments described herein and examples provided are merely illustrative and are not intended to be limiting. Many variations and modifications of the invention disclosed herein are contemplated and are within the scope of the present invention. The scope of protection is not limited by the above description, but only by the following claims, which scope includes all equivalents of the subject matter of the claims.

[0202]

[0357] The disclosures of all patents, patent applications, and publications cited herein, to the extent that they provide exemplary, procedural, or other details supplementary to those set forth herein, are hereby incorporated by reference in their entireties.

[0203]

[0358] Amounts and other numerical data may be presented in the form of a range in this specification. It is to be understood that such a range format is used merely for convenience and brevity, and should be interpreted flexibly to include not only the numerical values ​​explicitly recited as the upper and lower limits of the range, but also all individual numerical values ​​or subranges subsumed within the range as if each numerical value and subrange were explicitly recited. For example, a numerical range of about 1 to about 4.5 should be interpreted not only to include the explicitly recited upper and lower limits of 1 to about 4.5, but also to include the individual numbers, e.g., 2, 3, 4, and subranges, e.g., 1 to 3, 2 to 4, etc. The same principle applies to a range reciting only one numerical value, such as "less than about 4.5," which should be interpreted to include all of the values ​​and ranges recited above. Moreover, such an interpretation should be applied regardless of the breadth of the range or the characteristics described.

[0204]

[0359] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the presently disclosed subject matter belongs. Although any methods, devices, and materials similar or equivalent to those described herein can be used in the practice or testing of the presently disclosed subject matter, representative methods, devices, and materials are described herein.

[0205]

[0360] Following long-standing patent law convention, the terms "a" and "an" mean "one or more" when used in this application, including the claims.

[0206]

[0361] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as being modified in all instances by the term "about." Accordingly, unless indicated to the contrary, the numerical parameters set forth in the specification and appended claims are approximations, values ​​that may vary depending upon the desired properties sought to be achieved by the subject matter of the present disclosure.

[0207]

[0362] As used herein, the terms "about" and "substantially," when referring to a value or amount of mass, weight, time, volume, concentration, or percentage, are meant to encompass variations from the specified amount of ±20%, in some embodiments ±10%, in some embodiments ±5%, in some embodiments ±1%, in some embodiments ±0.5%, and in some embodiments ±0.1%, as such variations are appropriate for carrying out the disclosed methods.

[0208]

[0363] As used herein, the terms "substantially vertical" and "substantially parallel" are meant to encompass variations within ±10° of each of the vertical and parallel directions, in some embodiments within ±5° of each of the vertical and parallel directions, in some embodiments within ±1° of each of the vertical and parallel directions, and in some embodiments within ±0.5° of each of the vertical and parallel directions.

[0209]

[0364] As used herein, the term "and / or," when used in the context of listing entities, refers to the entities being present either singly or in combination. Thus, for example, the phrase "A, B, C, and / or D" not only includes A, B, C, and D individually, but also any and all combinations and subcombinations of A, B, C, and D.

[0210] Abbreviation

[0365] Further abbreviations used throughout this application are listed below.

[0366] AW: Anode waste

[0367] cAW: calcined AW

[0368] CB: Carbon black

[0369] CEI: cathode electrolyte interphase

[0370] CW: Cathode waste

[0371] fAW: Flash AW

[0372] fCW: Flash CW

[0373] fLCO: Flash LCO

[0374] fNMC: Flash NMC

[0375] FJH: Flash Joule Heating

[0376] GHG: Greenhouse gas

[0377] Hydro: Hydrometallurgy

[0378] LCA: Life Cycle Analysis

[0379] LCO: Lithium cobalt oxide (LiCoO2)

[0380] LIB: Lithium-ion battery

[0381] NMC: Lithium Nickel Manganese Cobalt Oxide (LiNi x Mn y Co z O2, usually referred to as NMCxyz, e.g. NMC811)

[0382] R-CW: Recombined cathode material

[0383] Pyro: Pyrometallurgy

[0384] SEI: Solid electrolyte interphase.

[0211]

[0385] It should be noted that the nomenclature of the terms "LCO" and "NMC" utilized herein is consistent with the terminology used in the industry. In the case of a lithium cobalt oxide cathode, the term LCO includes lithium in the acronym. However, in the case of a lithium nickel-manganese-cobalt oxide cathode, the term NMC does not include lithium in the acronym. To avoid confusion, the term "NMC" as used herein is synonymous with the terms "Li-NMC" and "LNMC," which are examples of alternative terms used in the industry for lithium nickel-manganese-cobalt oxide (used in the cathode). In a fully charged battery, most of the lithium is present in the anode. In a discharged battery, most of the lithium is present in the cathode and very little in the anode. Thus, the amount of lithium in the cathode depends on the state of charge. Generally, the battery is expected to be discharged prior to recycling. Thus, most of the lithium ions are expected to be pushed to the cathode. Thus, for the NMC cathode, the battery can be adequately described as lithium nickel manganese cobalt, since it is expected to contain a large amount of lithium as the battery discharges. For the LCO, some of the lithium migrates from the cathode to the anode. However, even when the battery is in a fully charged state, some lithium is always present in the cathode, and this is especially true for the LCO structure.

[0212] References

[0386] Advincula, P. A., et al., “Flash Graphene from Rubber Waste,” Carbon, 2021, 178, 649-656 (“Advincula 2021”).

[0387] Algozeeb, W. A., et al., “Flash Graphene From Plastic Waste,” ACS Nano, 2020, 14, 15595-15604 (“Algozeeb 2020”).

[0388] Andre, D., et al. “Future Generations Of Cathode Materials: An Automotive Industry Perspective,” J. Mater. Chem. A, 2015, 3, 6709-6732 (“Andre 2015”).

[0389] Apatiga, L. M., et al., “Magnetic Behavior Of Cobalt Oxide Films Prepared By Pulsed Liquid Injection Chemical Vapor Deposition From A Metal-Organic Precursor,” Thin Solid Films, 2006, 496, 576-579 (“Apatiga 2006”).

[0390] Assefi, M., et al., “Pyrometallurgical Recycling Of Li-Ion, Ni-Cd And Ni-MH Batteries: A Minireview,” Curr. Opin. Green Sustain. Chem., 2020, 24, 26-31 (“Assefi 2020”).

[0391] Baldacchini, G., et al., “Point defects in lithium fluoride by EUV and soft X-rays exposure for X-ray microscopy and optical applications,” IEEE J. Sel. Top. Quantum Electron, 2004, 10, 1435 (“Baldacchini 2004”).

[0392] Beyer, H., et al., “Thermal And Electrochemical Decomposition Of Lithium Peroxide In Non-Catalyzed Carbon Cathodes For Li-Air Batteries,” Phys. Chem. Chem. Phys., 2015, 15, 11025-11037 (“Beyer 2013”).

[0393] Bouteau, G., et al., “Effect of standard light illumination on electrolyte’s stability of lithium-ion batteries based on ethylene and di-methyl carbonates,” Sci. Rep. 2019, 9, 135 (“Bouteau 2019”).

[0394] Chagnes, A., et al., “A Brief Review On Hydrometallurgical Technologies For Recycling Spent Lithium-Ion Batteries,” J. Chem. Technol. Biotechnol., 2013, 88, 1191-1199 (“Chagnes 2013”).

[0395] Chen, X., et al., “Sustainable Recovery Of Metals From Spent Lithium-Ion Batteries: A Green Process,” ACS Sustain. Chem. Eng., 2015, 3, 3104-3113 (“Chen 2015”).

[0396] Chen, W., et al., “Millisecond Conversion Of Metastable 2D Materials By Flash Joule Heating,” ACS Nano, 2021, 15, 1282-1290 (“Chen 2021”).

[0397] Chen, W., et al., “Laser-Induced Silicon Oxide For Anode-Free Lithium Metal Batteries,” Adv. Mater., 2020, 32, 2002850 (“Chen 2020”).

[0398] Dai, T., et al., “Synergy Of Lithium, Cobalt, And Oxygen Vacancies In Lithium Cobalt Oxide For Airborne Benzene Oxidation: A Concept Of Reusing Electronic Wastes For Air Pollutant Removal,” ACS Sustain. Chem. Eng., 2019, 7, 5072-5081 (“Dai 2019”).

[0399] Everbatt 2020: Dai, Q., et al., “A Closed-Loop Battery Recycling Cost And Environmental Impacts Model,” Argonnee National Laboratories, Energy Division, 2019, ANL-19 / 16 (“Everbatt 2020”).

[0400] Furushima, Y., et al., “Thermal Stability And Kinetics Of Delithiated LiCoO2,” J. Power Sources, 2011, 196, 2260-2263 (“Furushima 2011”)).

[0401] GREET 2020: Wang, M., et al., “Summary of Expansions and Updates in GREET 2020,” Argonnee National Laboratories, Energy Systems Division, 2020, ANL / ESD-20 / 9 (“GREET 2020”).

[0402] He, L.-P., et al., “Recovery Of Lithium, Nickel, Cobalt, And Manganese From Spent Lithium-Ion Batteries Using L-Tartaric Acid As A Leachant,” ACS Sustain. Chem. Eng., 2016, 5, 714-721 (“He 2016”).

[0403] Hu, X., et al., “Recovery Of Co, Ni, Mn, And Li From Li-Ion Batteries By Smelting Reduction - Part I: A Laboratory-Scale Study,” J. Power Sources, 2021, 483, 228936 (“Hu 2021”).

[0404] Jacoby, M, “It’s Time To Get Serious About Recycling Lithium-Ion Batteries,” Chem. Eng. News, 2020, 97 (“Jacoby 2020”).

[0405] Kabir, M., et al., “Degradation Mechanisms In Li-Ion Batteries: A State-Of-The-Art Review,” Int. J. Energy Res., 2017, 41, 1963-1986 (“Kabir 2017”).

[0406] Lee, C. K., et al., “Preparation Of LiCoO2From Spent Lithium-Ion Batteries,” J. Power Sources, 2002, 109, 17-21 (“Lee 2002”).

[0407] Li, J., et al., “Environmentally-Friendly Oxygen-Free Roasting / Wet Magnetic Separation Technology For In Situ Recycling Cobalt, Lithium Carbonate And Graphite From Spent LiCoO2 / Graphite Lithium Batteries,” J. Hazard. Mater., 2016, 302, 97-104 (“Li 2016”).

[0408] Li, L., et al., “Sustainable Recovery Of Cathode Materials From Spent Lithium-Ion Batteries Using Lactic Acid Leaching System,” ACS Sustain. Chem. Eng., 2017, 5, 5224-5233 (“Li 2017”).

[0409] Li, S., et al., “Structural Distortion-Induced Charge Gradient Distribution Of Co Ions In Delithiated Licoo2Cathode,” J. Phys. Chem. Lett., 2019, 10, 7537-7546 (“Li 2019”).

[0410] Li, W., “Review-An Unpredictable Hazard in Lithium-ion Batteries from Transition Metal Ions: Dissolution from Cathodes, Deposition on Anodes and Elimination Strategies,” J. Electrochem. Soc., 2020, 167, 090514 (“Li 2020”).

[0411] Luong, D. X., et al., “Gram-scale Bottom-Up Flash Graphene Synthesis,” Nature, 2020, 577, 647-651 (“Luong 2020”).

[0412] Lv, W., et al., “A Critical Review And Analysis On The Recycling Of Spent Lithium-Ion Batteries,” ACS Sustain. Chem. Eng., 2018, 6, 1504-1521 (“Lv 2018”).

[0413] Moro, F., et al., “Magnetic properties of cobalt oxide nanoparticles synthesised by a continuous hydrothermal method. J Magn. Magn, 2013, 348, 1-7 (“Moro 2013”).

[0414] Natarajan, S., et al., “Recycling Strategies For Spent Li-Ion Battery Mixed Cathodes,” ACS Energy Lett., 2018, 3, 2101-2103 (“Natarajan 2018”).

[0415] Nie, H., et al., “LiCoO2: Recycling From Spent Batteries And Regeneration With Solid State Synthesis,” Green Chem., 2015, 17, 1276-1280 (“Nie 2015”).

[0416] Pinna, E. G., et al., “Cathodes Of Spent Li-Ion Batteries: Dissolution With Phosphoric Acid And Recovery Of Lithium And Cobalt From Leach Liquors,” Hydrometallurgy, 2017, 167, 66-71 (“Pinna 2017”).

[0417] “Recycle Spent Batteries,” Nat. Energy, 2019, 4, 253-253 (“Recycle 2019”).

[0418] Salvatierra, R. V., et al., “What Can Be Expected From ‘Anode-Free’ Lithium Metal Batteries?” Adv. Energy Sustain. Res., 2021, 2, 202000110 (“Salvatierra 2021”).

[0419] Sharifi-Asl, S., et al., “Facet-Dependent Thermal Instability In LiCoO2,” Nano Lett, 2015, 17, 2165-2171 (“Sharifi-Asl 2017”).

[0420] Swain, B., et al., “Hydrometallurgical Process For Recovery Of Cobalt From Waste Cathodic Active Material Generated During Manufacturing Of Lithium Ion Batteries,” J. Power Sources, 2007, 167, 536-544 (“Swain 2007”).

[0421] Tran, M. K., et al., “Deep Eutectic Solvents For Cathode Recycling Of Li-Ion Batteries,” Nat. Energy, 2019, 4, 339-345 (“Tran 2019”).

[0422] Universal Matter, “Scaleup Of FJH For Graphene Synthesis,” from domain name www.universalmatter.com, 2021 (“Universal Matter 2021”).

[0423] Velazquez, M., et al., “A Critical Review Of Lithium-Ion Battery Recycling Processes From A Circular Economy Perspective,” Batteries, 2019, 5, 68 (“Velazquez 2019”).

[0424] Wang, D., et al., “Separation Of Li And Co From The Active Mass Of Spent Li-Ion Batteries By Selective Sulfating Roasting With Sodium Bisulfate And Water Leaching,” Miner. Eng., 2018, 126, 28-35 (“Wang 2018”).

[0425] Xiao, J., et al., “Recycling Metals From Lithium Ion Battery By Mechanical Separation And Vacuum Metallurgy,” J. Hazard. Mater., 2017, 338, 124-131 (“Xiao I 2017”).

[0426] Xiao, J., et al., “Novel Approach For In Situ Recovery Of Lithium Carbonate From Spent Lithium Ion Batteries Using Vacuum Metallurgy,” Environ. Sci. Technol., 2017, 51, 11960-11966 (“Xiao II 2017”).

[0427] Xu, P., et al., “Efficient Direct Recycling Of Lithium-Ion Battery Cathodes By Targeted Healing,” Joule, 2020, 4, 2609-2626 (“Xu 2020”).

[0428] Yu, H., et al., “Mechanistic insights into the lattice reconfiguration of the anode graphite recycled from spent high-power lithium-ion batteries,” J. Power Sources, 2021, 481, 229159 (“Yu 2021”).

[0429] Zhang, C., et al., “Closed-Edged Graphene Nanoribbons From Large-Diameter Collapsed Nanotubes,” ACS Nano, 2012, 6, 6023-6032 (“Zhang 2012”).

[0430] Zhang, D., et al., “Controllable Fabrication And Magnetic Properties Of Double-Shell Cobalt Oxides Hollow Particles,” Sci. Rep., 2015, 5, 8737 (“Zhang 2015”).

[0431] Zhang, P., et al., “Hydrometallurgical Process For Recovery Of Metal Values From Spent Lithium-Ion Secondary Batteries,” Hydrometallurgy, 1998, 47, 259-271 (“Zhang 1998”).

[0432] Zhang, Z., et al., “Recovery Of Lithium Cobalt Oxide Material From The Cathode Of Spent Lithium-Ion Batteries,” ECS Electrochem. Lett., 2014, 3, A58-A61 (“Zhang 2014”).

[0433] Zhao, Y., et al., “Regeneration And Reutilization Of Cathode Materials From Spent Lithium-Ion Batteries,” Chem. Eng. J., 2020, 383, 123089 (“Zhao 2020”).

[0434] Zou, H., et al., “A Novel Method To Recycle Mixed Cathode Materials For Lithium Ion Batteries,” Green Chem., 2013, 15, 1183 (“Zou 2013”)。

Claims

1. 1. A method for recovering metals comprising the steps of: (a) forming a mixture including a cathode material, the cathode material being prepared from one or more batteries; (b) applying a voltage across the mixture to obtain metals and cathode waste from the cathode material, (i) the voltage is applied in one or more voltage pulses; (ii) the duration of each of the one or more voltage pulses is for a period of predetermined duration; and (c) magnetically separating the metal and the cathode waste; The above method.

2. 10. The method of claim 1, wherein the metal comprises a cathode metal selected from the group consisting of lithium, cobalt, nickel, manganese, iron, and combinations thereof.

3. The method of claim 1 , wherein the metal comprises a cathodic metal selected from the group consisting of metal oxides, metal salts, metal carbonates, metal phosphates, and combinations thereof.

4. The method of claim 3 , wherein the cathode metal comprises a metal oxide.

5. The method of claim 3 , wherein the cathode metal comprises a metal carbonate.

6. The method of claim 3 , wherein the cathode metal comprises a metal phosphate.

7. The method of claim 1 , wherein the one or more batteries comprise one or more lithium ion batteries.

8. 8. The method of claim 7, wherein each of the one or more lithium ion batteries comprises a respective LCO cathode.

9. 8. The method of claim 7, wherein each of the one or more lithium ion batteries comprises an NMC cathode.

10. The method of claim 1 , wherein the mixture further comprises a conductive additive.

11. The method of claim 1 , wherein the cathode material preserves the 3D layer structure of the cathode.

12. 10. The method of claim 1 further comprising a step of cooling, said step cooling said metal and said cathode waste prior to the step of magnetically separating said metal and said cathode waste.

13. further comprising applying a second voltage across the cathode waste after the mechanically separating step; (a) the second voltage is applied in one or more second voltage pulses; 2. The method of claim 1, wherein (b) a duration of each of the one or more second voltage pulses is for a second predetermined period of time.

14. (a) applying the second voltage across the cathode waste captures additional metal and a reduced portion of the cathode waste; 14. The method of claim 13, wherein the method further comprises the step of: (b) magnetically separating the additional metal and the reduced portion of the cathode waste.

15. A system for carrying out a method for recovering metals utilizing at least one of the methods according to claims 1 to 14, comprising: (a) a source of a mixture comprising a cathode material; (b) a cell operably connected to said source such that said mixture flows into said cell and is held under compression; (c) an electrode operably connected to the cell; (d) a flash power supply for applying a voltage across the mixture to obtain metal and cathode waste from the cathode material; (e) a magnet in operative contact with said metal and said cathode waste, said magnet being operable in response to the step of magnetically separating said metal and said cathode waste; The above system.